Polyethylene and film containing same
By using metallocene catalysts with specific structures and advanced analytical techniques, polyethylene with a density between 0.916g/cm3 and 0.920g/cm3 was prepared, which solved the problem of scaling and density reduction in linear low-density polyethylene in the slurry polymerization process, and achieved excellent mechanical characteristics and processing properties of polyethylene.
Patent Information
- Application Number
- CN202380044998.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-13
- Filing Date
- 2023-12-15
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, linear low-density polyethylene is prone to scale in the slurry polymerization process, and in the film production process, the use of anti-blocking agent needs to be increased due to viscosity, resulting in a decrease in density and affecting its mechanical characteristics and processing performance.
By using a metallocene catalyst with a specific structure, polyethylene with excellent control of short-chain branch content and distribution was prepared, combined with temperature-raising elution framing and Fourier transform infrared spectroscopy, the density of the polyethylene was ensured between 0.916 g/cm3 and 0.920 g/cm3.
The excellent mechanical properties of polyethylene are achieved, including improved transparency and dart impact strength, while having excellent processing properties and thinning during film production.
Smart Images

Figure CN119654354A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is based on and claims the benefit of priority of Korean Patent Application Nos. 10-2022-0176237 and 10-2023-0181010, filed on Dec. 15, 2022 and Dec. 13, 2023, respectively, the contents of which are hereby incorporated by reference in their entirety.
[0003] The present invention relates to polyethylene and films containing the same, wherein the polyethylene exhibits transparency, dart impact strength characteristics, and excellent processability and can be thinned during film production. Background Art
[0004] Linear low-density polyethylene (LLDPE) is produced by copolymerization of ethylene and α-olefin using a polymerization catalyst under low pressure. It is a resin with a narrow molecular weight distribution, short-chain branches of a certain length, and no long-chain branches.
[0005] Linear low-density polyethylene films have high breaking strength and elongation, excellent film processability and transparency, excellent tear strength and dart impact strength, and common properties of polyethylene. Therefore, they are increasingly used in food packaging and industrial films (such as industrial composite films, durable films, and stretch wrapping films), while existing low-density polyethylene or high-density polyethylene is difficult to use in these fields.
[0006] It is well known that the dart impact strength of linear low-density polyethylene generally increases with decreasing density. However, when a large amount of comonomer is used to prepare low-density polyethylene, there are problems such as increased fouling frequency in the slurry polymerization process and increased use of anti-blocking agents due to sticking phenomena when producing films comprising the low-density polyethylene. In addition, there is also the problem of decreased bulk density due to process instability during production or due to decreased morphological characteristics of the produced polyethylene.
[0007] Recently, due to the market trend of sustainability and D4R (Design For Recyclability), the demand for down-gauging is increasing, and thus the demand for linear low-density polyethylene having excellent processability and dart drop impact strength is also increasing.
[0008] Dart impact strength is a very important mechanical property that determines the resistance of the resin to various impacts.
[0009] Linear low-density polyethylene has excellent mechanical properties; however, it has the disadvantages of poor processability and reduced transparency in the production of blown films. Blown film is a film made by blowing air into molten plastic to expand, also known as expanded film.
[0010] Typically, linear low density polyethylene exhibits improved transparency and increased dart impact strength as density decreases. However, when a large amount of α-olefin comonomer is used to prepare low density polyethylene, there are the following problems: in the slurry polymerization process, scaling is often generated, and when producing films containing the low density polyethylene, the use of anti-blocking agents must be increased due to sticking phenomena. In addition, there is also the problem of decreased bulk density due to process instability during production or due to decreased morphological characteristics of the produced polyethylene. Therefore, in the slurry polymerization process, the main production density is 0.915 g / cm 3 The above products.
[0011] Therefore, it is necessary to achieve excellent mechanical properties (such as dart impact strength, etc.) and transparency as well as excellent processing performance while having a density of 0.915 g / cm 3 Polyethylene above. Summary of the invention
[0012] Technical issues
[0013] In order to solve the problems existing in the prior art, the present invention provides a polyethylene which can be thinned, has improved transparency and dart impact strength characteristics and excellent processing performance.
[0014] Also provided is a film exhibiting excellent processability and transparency as well as dart impact strength characteristics by including the polyethylene.
[0015] Technical Solution
[0016] According to the present invention, there is provided a polyethylene, wherein when the polyethylene is subjected to temperature-increasing elution fractionation and Fourier transform infrared spectroscopy analysis, the absolute value of the slope a in the first-order linear relationship y=ax+b derived from the curve of the change in the number of SCB (short chain branches) with the elution temperature is 0.5 to 0.6, and the density measured according to the ASTM D1505 standard is 0.916 g / cm 3 Up to 0.920g / cm 3 .
[0017] According to the present invention, there is also provided a film comprising the polyethylene.
[0018] Beneficial Effects
[0019] The polyethylene of the present invention exhibits transparency and dart impact strength properties, while having excellent processability and being capable of being thinned during film production. Therefore, it can be used as a film for food, agricultural and general industrial purposes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A graph showing the relationship between the elution temperature (Te) (° C.) from the cross fractionation chromatography (CFC) analysis results of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 and the weight average molecular weight (Mw) (g / mol) of each eluted polymer.
[0021] Figure 2a A graph showing the relationship between the elution temperature (Te) (°C) and the number of SCBs (CH3 / 1000C) from the CFC analysis results of the polyethylenes of Examples 1 to 4.
[0022] Figure 2b A graph showing the relationship between the elution temperature (Te) (°C) and the SCB number (CH3 / 1000C) from the CFC analysis results of the polyethylenes of Comparative Examples 1 to 4.
[0023] Figure 3 Shown are relaxation time spectra of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 measured using a rotational rheometer (ARES-G2 Rheometer, manufactured by TA Instruments).
[0024] Figures 4 to 11 They are shown respectively Figure 3 Deconvoluted graphs of relaxation time spectra of Examples 1 to 4 and Comparative Examples 1 to 4.
[0025] Fig.12 A graph showing the relationship between the loss modulus (G") and the storage modulus (G') obtained from the measurement results of the rheological properties of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 is shown.
[0026] Fig.13 A graph showing the relationship between the storage modulus (G') and the complex viscosity (η*) obtained from the measurement results of the rheological properties of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 is shown. DETAILED DESCRIPTION
[0027] As used in the present invention, the terms "first" and "second" and the like are used to describe various components, and these terms are only used to distinguish a certain component from other components.
[0028] In addition, the terms used in this specification are only used to explain the exemplary embodiments and are not intended to limit the present invention. Unless there is a different expression in the context, a singular expression may include a plural expression. It must be understood that the terms "including", "equipped with" or "having" in this specification are only used to indicate the existence of the features, quantities, steps, components or combinations thereof that are in effect, and do not exclude the possibility of the prior existence or addition of one or more different features, quantities, steps, components or combinations thereof.
[0029] In addition, in the present specification, the term "polyethylene" or "ethylene (co)polymer" is a concept including an ethylene homopolymer and / or a copolymer of ethylene and an α-olefin.
[0030] The present invention can be modified in various ways and has various forms, and specific embodiments will be described in detail below. However, it should be understood that the description is not intended to limit the present invention to the specific forms disclosed, but rather, is intended to cover all modifications, equivalents, and alternatives that fall within the spirit and scope of the present invention.
[0031] Hereinafter, the polyethylene of the present invention and a film including the same will be described in detail.
[0032] Specifically, when the polyethylene of the present invention is subjected to temperature-increasing elution fractionation and Fourier transform infrared spectroscopy analysis, the absolute value of the slope a in the first-order linear relationship y=ax+b obtained from the curve of the change of the number of SCB (branching / 100°C) with the elution temperature (Te) (°C) is 0.5 to 0.6, and
[0033] Density measured according to ASTM D1505 is 0.916 g / cm 3 Up to 0.920g / cm 3 .
[0034] As used herein, SCB (short chain branch) refers to a short chain connected to the polyethylene main chain in the form of a branch, specifically, a chain with 2 to 7 carbon atoms. SCB is a short chain branch produced when an α-olefin (such as 1-butene, 1-hexene or 1-octene) with more than 4 carbon atoms is used as a comonomer, and its content can be proportional to the content of the α-olefin monomer contained in the polymer chain. The SCB content refers to the number of chain branches with 2 to 7 carbon atoms per 1000 carbon atoms (unit: branch / 1000C or CH3 / 1000C), which can be calculated by nuclear magnetic resonance hydrogen spectrum (1H-NMR) or Fourier transform infrared spectroscopy (FT-IR) analysis. In the present invention, the SCB content is calculated by FT-IR analysis, and the detailed analysis method will be described in the following experimental examples.
[0035] Polyethylene is a semi-crystalline polymer that may contain crystalline regions and non-crystalline regions. In the crystalline regions, polymer chains containing ethylene repeating units or α-olefin repeating units fold into bundles to form crystalline blocks (or segments) in the form of lamellars.
[0036] This crystalline mass in the form of flakes affects the physical properties of polyethylene, especially dart impact strength and clarity, and SCB favors the formation of such flakes. Therefore, with higher SCB content in polyethylene and more multimodal distribution of flakes, the polyethylene shows a significant improvement in dart impact strength while maintaining clarity compared to existing polyethylene of the same density.
[0037] In the present invention, a metallocene catalyst having a specific structure is used to prepare polyethylene having an optimally controlled SCB content or distribution and a molecular weight according to crystallinity, so that the prepared polyethylene has improved transparency and dart impact strength characteristics, and excellent processing properties, and thus can be thinned during film production.
[0038] Meanwhile, in temperature rising elution fractionation (TREF) analysis, the width of the TREF curve and the elution temperature indicate the uniformity of SCB distribution. For polyethylene with the same density, the narrower the TREF curve, the more uniform the SCB distribution, because polymer chains with different molecular weights have similar numbers of SCBs.
[0039] Therefore, in the present invention, the relationship between elution temperature and SCB number, and the effect of this relationship on dart impact strength and polyethylene transparency are determined by TREF and FT-IR analysis, which is defined by the absolute value of the slope a in the first-order linear relationship y=ax+b obtained by the curve of the change of SCB number with elution temperature.
[0040] Specifically, TREF and FT-IR analyses were performed on polyethylene, and the analysis results were plotted with the elution temperature (Te) (°C) as the x-axis and the number of SCB (the number of chain branches containing 2 to 7 carbon atoms per 1000 carbon atoms, unit: branch / 1000C (or CH3 / 1000C)) as the y-axis. The obtained curve of the change of the number of SCB with the elution temperature was fitted, and a first-order linear relationship y=ax+b was derived, thereby obtaining the slope (a) and its absolute value defined above.
[0041] The absolute value of the slope in the curve of SCB number versus elution temperature indicates the distribution of polyethylene short chain branches (SCBD), and the dart impact strength characteristics of polyethylene can be predicted by this distribution. Specifically, the smaller the absolute value of the slope obtained from the curve of SCB number versus elution temperature, the lower the SCB content in the low crystalline region; the larger the absolute value of the slope, the higher the SCB content in the low crystalline region, and the lower the SCB content in the high crystalline region.
[0042] Therefore, in the present invention, excellent impact strength properties are achieved by increasing the SCB content of the low crystalline region, and transparency is improved by controlling the SCB content and molecular weight of the high crystalline region.
[0043] Conventionally, the orthogonal comonomer distribution (BOCD) structure is defined and optimized as the BOCD index, because when polyethylene has a wider orthogonal comonomer distribution (BOCD) structure, it means that it has a higher SCB content in the high molecular weight region, showing excellent impact strength characteristics. However, the BOCD index does not take into account the crystallinity of the polymer, and the SCB distribution based on molecular weight is not suitable for use as an index for determining impact strength and transparency. In contrast, the absolute value of the slope of the curve of the change in the SCB number with the elution temperature defined in the present invention can represent the inherent physical properties of the polymer based on the catalyst structure, reaction process conditions, film forming conditions, etc., and therefore, the SCBD characteristics of polyethylene are defined, which is more conducive to predicting the drop dart impact strength and then predicting the transparency.
[0044] Regarding the polyethylene of the present invention, the absolute value of the slope of the curve of the SCB number versus elution temperature is 0.5 to 0.6, and therefore, it can exhibit excellent dart impact strength and transparency. More specifically, the absolute value is 0.5 or more, or 0.52 or more, or 0.54 or more, or 0.541 or more, or 0.545 or more, and 0.6 or less, or 0.595 or less, or 0.593 or less, or 0.56 or less.
[0045] Meanwhile, in the present invention, the TREF analysis of polyethylene can be performed using the TREF device of PolymerChar, with 1,2,4-trichlorobenzene as solvent, in the range of 35°C to 120°C. Specifically, 32 mg of polyethylene sample was dissolved in 8 mL of 1,2,4-trichlorobenzene solvent, heated at 160°C for 90 minutes, and then stabilized at 140°C for 20 minutes. The solution was introduced into the TREF column, and then cooled from 140°C to 35°C at a cooling rate of 0.5°C / min, and maintained for 15 minutes. Thereafter, while heating from 35°C to 120°C at a rate of 1°C / min, the solvent 1,2,4-trichlorobenzene was applied to the column at 0.2 mL / min to measure the concentration of the eluted polymer fraction. According to the concentration measurement results, a TREF analysis graph was drawn with the elution temperature (Te) (°C) as the x-axis and the weight average molecular weight (Mw) (g / mol) of the polymer as the y-axis, and the elution temperature (Te) (°C) corresponding to the highest point of the peak was determined.
[0046] In addition, in the present invention, the SCB amount (the content of chain branches with 2 to 7 carbon atoms per 1000 carbons, branches / 1000C) of the molecules eluted at each temperature can be determined by analyzing polyethylene by FT-IR. The FT-IR for SCB measurement can use, for example, a PerkinElmer Spectrum 100 device containing a DTGS detector at a test temperature of 100°C to 200°C (specifically 160°C) and a wavelength of 2000cm -1 Up to 4000cm -1 , specifically, 2700cm -1 Up to 3000cm -1 , scan times range from 1 to 20, resolution 1cm -1 Up to 10cm -1 under the conditions of.
[0047] In the present invention, the analysis method and conditions of TREF analysis and FT-IR analysis, and the method of obtaining the variation curve of SCB quantity with elution temperature (Te) (°C) and its first-order linear relationship will be described in detail in the following experimental examples.
[0048] In addition, the polyethylene of the present invention further satisfies the following conditions (a1) to (a3) in the TREF analysis:
[0049] (a1) a weight average molecular weight (Mw) of a low crystalline polymer fraction (M1) eluted at an elution temperature of 35° C. to 70° C.: 110,000 g / mol or more, more specifically 110,000 g / mol or more, or 115,000 g / mol or more, or 117,000 g / mol or more, or 120,000 g / mol or more, and 170,000 g / mol or less, or 165,000 g / mol or less, or 163,000 g / mol or less, or 130,000 g / mol or less;
[0050] (a2) a weight average molecular weight (Mw) of a high crystalline polymer fraction (M3) eluted at an elution temperature of 90° C. or higher: 110,000 g / mol or higher, more specifically 110,000 g / mol or higher, or 130,000 g / mol or higher, or 150,000 g / mol or higher, or 151,000 g / mol or higher, or 160,000 g / mol or higher, and 200,000 g / mol or lower, or 190,000 g / mol or lower, or 186,000 g / mol or lower, or 180,000 g / mol or lower; and
[0051] (a3) The ratio of the weight average molecular weight of M3 to the weight average molecular weight of M1 (M3 Mw / M1 Mw ): 0.9 or more, more specifically, 0.9 or more, or 0.92 or more, or 0.925 or more, or 0.928 or more, or 0.93 or more, or 1 or more, and 1.7 or less, or 1.6 or less, or 1.55 or less, or 1.52 or less, or 1.515 or less, or 1.51 or less.
[0052] The above conditions (a1) to (a3) mean that the polyethylene has a bimodal crystal distribution characteristic with different molecular weight distributions. The polyethylene according to the present invention, by controlling the molecular weight distribution according to this crystal distribution, exhibits a wider polydispersity and a bimodal relaxation time spectrum, and is therefore able to exhibit excellent dart impact strength characteristics and improved haze characteristics. The molecular weight of M1 refers to the molecular weight of the low crystalline region polymer fraction, which is related to the formation of the tie molecules, thereby affecting the impact strength. In addition, the molecular weight of M3 refers to the molecular weight of the high crystalline region polymer fraction, which is related to the crystallinity during the film formation process, thereby affecting the transparency of the film. Therefore, the haze and impact strength properties can be improved simultaneously by adjusting the ratio of M3 to M1.
[0053] In addition, when the polyethylene of the present invention is subjected to TREF analysis, the weight average molecular weight (Mw) of the medium crystalline polymer fraction (M2) eluted at an elution temperature of 70°C to 90°C may be 120,000 g / mol or less, more specifically, 120,000 g / mol or less, or 110,000 g / mol or less, or 108,000 g / mol or less, or 107,000 g / mol or less, or 100,000 g / mol or less, and 80,000 g / mol or more, or 85,000 g / mol or more, or 86,000 g / mol or more, or 95,000 g / mol or more.
[0054] In the present invention, the weight average molecular weight (Mw) of the fraction eluted at each temperature in the TREF analysis can be measured by GPC analysis. Specifically, the fraction eluted at each temperature in the TREF analysis is transferred to a GPC column (Polymer Laboratories PLgel MIX-B 300 mm length column) of a GPC instrument (Waters PL-GPC220), and the analysis can be performed under the following conditions: the measurement temperature is 100°C to 200°C (specifically 160°C), the solvent is 1,2,4-trichlorobenzene, the flow rate is 0.1mL / minute to 10mL / min (specifically 1mL / min), wherein the sample concentration is 1mg / 10mL to 20mg / 10mL (specifically 10mg / 10mL), and the amount is 100μL to 300μL (specifically 200μL). The Mw value is obtained by a calibration curve obtained using a polystyrene standard sample, wherein the weight average molecular weight of the polystyrene standard sample can be 9 kinds, for example, 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol and 10000000 g / mol.
[0055] The GPC analysis method and conditions of the present invention will be described in more detail in the following experimental examples.
[0056] In addition, when the polyethylene of the present invention is subjected to relaxation time spectrum analysis, it shows a bimodal crystal distribution in a graph with the x-axis being relaxation time (τ) (s) and the y-axis being τH(τ) / η0, wherein s represents the time unit "second".
[0057] This crystal distribution means that the content of high molecular weight polymer with long relaxation time is higher than that of polyethylene showing a unimodal crystal distribution. Therefore, it is easy to control the crystal growth rate, thereby obtaining excellent dart impact strength and transparency.
[0058] In addition, when the polyethylene was subjected to relaxation time spectrum analysis, the relaxation spectrum index (RSI) calculated according to the following Equation 1 was 29 to 43.
[0059] [Equation 1]
[0060]
[0061] In equation 1, G is calculated according to the following equations (i) and (ii) respectively: I and G II ,
[0062]
[0063]
[0064] In equations (i) and (ii), N represents the number of modes in the modal distribution of the relaxation time spectrum, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ), τ i represents the relaxation time (s).
[0065] Specifically, G in Equation 1 I and G II are the first moment and second moment of the relaxation time spectrum modal distribution, respectively. After calculating the modal distribution of the relaxation time spectrum, the first moment and second moment of the distribution similar to Mn and Mw can be calculated.
[0066] The relaxation time spectra are calculated from experimental results of measured material constants.
[0067] Specifically, a shear strain is applied to the polyethylene and the response to the strain is measured using a rheometer, and then, based on the response of the polyethylene and the structure and shape of the rheometer used, the relaxation modulus G(t) or the dynamic modulus (storage modulus (G'(ω)) and loss modulus (G"(ω))) can be determined as a function of time (t) or frequency (ω), respectively (see JM Dealy and KF Wissbrun, Melt Rheology and Its Role in Plastics Processing, Van Nostrand Reinhold, 1990, pp. 269-297).
[0068] The relaxation time spectrum can be expressed in continuous or discontinuous form. After obtaining G'(ω) and G"(ω), the spectrum factor is used for analysis. The continuous relaxation time spectrum is obtained by the following integral calculation, while the discrete relaxation time spectrum (or discontinuous relaxation time spectrum) is obtained by dividing and calculating according to the specified division number, that is, the modulus (N) as follows (Seungjoon Park et al., The Korean J. of Rheology, 1996 (8) 103-118).
[0069] <Continuous relaxation time spectrum, H(t)>
[0070]
[0071]
[0072] <Discrete relaxation time spectrum, G i >
[0073]
[0074]
[0075] In equations (1) to (4), G'(ω) represents the storage modulus, and G"(ω) represents the loss modulus.
[0076] In addition, H(τ) represents the relaxation time spectrum, ω represents the frequency (rad / s), τ represents the continuous relaxation time (s), and τ i represents the discrete relaxation time (s).
[0077] In addition, Nb represents the modulus, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ).
[0078] The modal distribution of the relaxation spectrum can also be calculated by software such as IRIS Rheology Software (manufactured by IRIS Development). Once the modal distribution in the relaxation spectrum is calculated, the first and second moments of the distribution (similar to the first and second moments Mn and Mw of the molecular weight distribution) can be calculated as follows.
[0079]
[0080] In equations (i) and (ii), N represents the mode number in the relaxation time spectrum, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ), τ i represents the relaxation time (s).
[0081] In the present invention, the RSI of polyethylene is obtained by the method proposed by Wasserman (S,.H.Wassermna ANTEC 1997,55,1129). Specifically, it can be obtained by using the G calculated in equations (i) and (ii) according to equation 1. I and G II Value obtained.
[0082] The elasticity of a fluid is related to the second moment in the modal distribution of the relaxation spectrum, so the RSI is also a measure of elasticity.
[0083] RSI is sensitive to parameters such as molecular weight distribution, molecular weight and long chain branching of the polymer. The higher the RSI value, the wider the relaxation time distribution of the polyethylene, resulting in better processing performance and haze performance. However, when the RSI value is too high, it means that the elasticity of the polymer is very high, the bubble stability is reduced during the thinning process, or the impact strength is reduced or melt fracture is caused by increased orientation during the film forming process, so it is believed that the haze characteristics may deteriorate. In addition, when the RSI is too low, due to the low elasticity of the polymer, the stability during film processing may be reduced, or due to the increase in film thickness deviation, the smoothness of the film may be reduced, and therefore, it is believed that the impact strength may deteriorate.
[0084] The relaxation spectrum index (RSI) of the polyethylene of the present invention is 29 or more, or 29.1 or more, or 29.15 or more, or 29.19 or more, or 30 or more, and 43 or less, or 42.5 or less, or 42.1 or less, or 42.01 or less, or 40 or less. Since the RSI value of the polyethylene is within this range, excellent processability and haze characteristics can be exhibited.
[0085] In addition, when the polyethylene of the present invention is subjected to relaxation time spectrum analysis, the weighted average relaxation time (τ w ) is 1.2 seconds to 10 seconds.
[0086] [Equation 2]
[0087]
[0088] In Equation 2, N represents the modulus, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ), τ i represents the relaxation time (s).
[0089] Since the weighted average relaxation time (τ w) satisfies the above-mentioned range, and the presence of the high molecular weight polymer makes it easier to control the crystal speed during the film forming process, so that excellent haze characteristics can be exhibited. More specifically, the weighted average relaxation time is 1.2 seconds or more, or 1.22 seconds or more, 10 seconds or less, or 9.8 seconds or less.
[0090] In addition, the zero shear viscosity (η0) can be calculated using the relaxation time. Specifically, the zero shear viscosity (η0) of polyethylene calculated according to the following formula 3 based on the results of relaxation time spectrum analysis is 9000 Pa·s or more and 13000 Pa·s or less.
[0091] [Equation 3]
[0092]
[0093] In Equation 3, N represents the modulus, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ), τ i represents the relaxation time (s).
[0094] More specifically, the zero shear viscosity is 9000 Pa·s or more, or 9100 Pa·s or more, or 9200 Pa·s or more, or 9500 Pa·s or more, and 13000 Pa·s or less, or 12800 Pa·s or less, or 12650 Pa·s or less, or 12000 Pa·s or less.
[0095] Furthermore, when polyethylene is subjected to relaxation time spectrum analysis, the highest peak of the relaxation time spectrum appears when the relaxation time (τ) is 0.05 to 1 second.
[0096] The appearance of the highest peak means that the relaxation time is longer. More specifically, the highest peak of the relaxation time spectrum appears at more than 0.05 seconds, or more than 0.09 seconds, or more than 0.098 seconds, or more than 0.1 seconds, and less than 1 second, or less than 0.5 seconds, or less than 0.3 seconds, or less than 0.2 seconds, or less than 0.174 seconds.
[0097] Furthermore, when polyethylene is subjected to relaxation time spectrum analysis, the full width at half maximum (FWHM) of the peak appearing at a relaxation time (τ) of 1 to 10 seconds, that is, the FWHM of the peak of 1s≤τ≤10s is 0.95 to 2.0, and the ratio of the area of the peak appearing at a relaxation time (τ) of 1 to 10 seconds to the total peak area of the relaxation time spectrum (=area of the peak of 1s≤τ≤10s / total peak area of the relaxation time spectrum) is 14% to 40%.
[0098] More specifically, the FWHM of the peak appearing when the relaxation time (τ) is 1 second to 10 seconds is 0.95 or more, or 0.99 or more, or 1.0 or more, or 1.22 or more, and 2.0 or less, or 1.95 or less, or 1.9 or less, or 1.5 or less, or 1.29 or less. In addition, the ratio of the peak area of the relaxation time spectrum to the total peak area is 14% or more, or 14.2% or more, and 40% or less, or 35% or less.
[0099] The peak appearing at a relaxation time (τ) of 1 to 10 seconds means the presence of a polymer having a relatively long relaxation time.
[0100] In addition, the influence on the processability and haze characteristics of polyethylene is also predicted by the FWHM and peak area ratio of the peak. When the FWHM of the peak is too low, it means that the relaxation time distribution is very narrow; when the FWHM of the peak is too high, it means that the relaxation time distribution is very wide. In addition, when the ratio of the peak area to the total peak area of the relaxation time spectrum (peak area of 1s≤τ≤10s / total peak area of the relaxation time spectrum) is too low or 0, it means that the polymer content with a long relaxation time is low or does not exist, and when the ratio is too high, it means that the polymer content with a long relaxation time is high. RSI depends on the presence and distribution characteristics of the peak, which ultimately affects the bubble stability caused by crystallization speed and elasticity during film formation. In addition, since RSI affects the monodispersity of polymer melt, it also affects processing performance. The polyethylene of the present invention can exhibit excellent processability and haze performance because it meets the FWHM and peak area ratio of the above-mentioned peaks.
[0101] In addition, when the polyethylene of the present invention is subjected to continuous self-nucleation and annealing (SSA) analysis, the following conditions (c1) to (c3) are satisfied:
[0102] (c1) f1 (<100°C) (ratio of the peak area with a melting temperature below 100°C to the total peak area): 0.35 to 0.41, more specifically, 0.35 or more, or 0.36 or more, or 0.365 or more, or 0.3673 or more, and 0.41 or less, or 0.408 or less, or 0.4065 or less, or 0.4063 or less;
[0103] (c2)f2 (100-120°C) (ratio of the peak area with a melting temperature of 100°C to 120°C to the total peak area): 0.30 to 0.38, more specifically, 0.30 or more, or 0.305 or more, or 0.307 or more, and 0.38 or less, or 0.35 or less, or 0.34 or less, or 0.3353 or less; and
[0104] (c3)f3(>120℃) (ratio of the peak area with melting temperature higher than 120℃ to the total peak area): 0.24 to 0.33, more specifically, above 0.24, or above 0.25, or above 0.28, or above 0.2827, or above 0.285, and below 0.33, or below 0.325, or below 0.3234, or below 0.3.
[0105] f1, f2 and f3 respectively refer to the proportion of crystals according to the comonomer distribution in the polymer, and by satisfying the above requirements of the peak area ratio according to the melting temperature, the polyethylene can exhibit excellent dart impact strength characteristics.
[0106] In addition, when conducting SSA analysis on polyethylene, the following conditions (c4) to (c6) may also be met:
[0107] (c4) f2 / f1: 0.7 to 0.9, more specifically, 0.7 or more, or 0.75 or more, or 0.76 or more, or 0.79 or more, and 0.9 or less, or 0.88 or less, or 0.85 or less;
[0108] (c5) f3 / f1: 0.6 or more, more specifically, 0.6 or more, or 0.65 or more, or 0.7 or more, and 1 or less, or 0.9 or less, or 0.88 or less, or 0.8 or less; and
[0109] (c6) f3 / f2: 0.8 or more, more specifically, 0.8 or more, or 0.85 or more, or 0.9 or more, and 1.5 or less, or 1.2 or less, or 1.05 or less, or 1 or less.
[0110] f2 / f1 refers to the ratio of the medium crystalline region to the low crystalline region, f3 / f1 refers to the ratio of the high crystalline region to the low crystalline region, and f3 / f2 refers to the ratio of the high crystalline region to the medium crystalline region. When these ratios meet the above-mentioned optimal requirements, more excellent dart impact strength characteristics can be exhibited.
[0111] As mentioned above, polyethylene is a semi-crystalline polymer comprising a crystalline region and a non-crystalline region. In the crystalline region, polymer chains comprising ethylene repeating units or α-olefin repeating units are folded into bundles to form crystalline blocks (or segments) in the form of lamellar layers. At this time, the ethylene repeating units forming the lamellar crystals are ethylene sequences.
[0112] Continuous self-nucleation and annealing (SSA) is a method that uses differential scanning calorimetry (DSC) to reduce the temperature in stages and cool at the end of each stage to retain the crystals that crystallized at the corresponding temperature of each stage.
[0113] In other words, polyethylene is completely melted by heating and then cooled to a specific temperature (T). When slowly annealed, the unstable lamellae at the corresponding temperature (T) still melt and only the stable lamellae crystallize. Therefore, the stability at the corresponding temperature (T) depends on the thickness of the lamellae, and the thickness of the lamellae depends on the structure of the chain. Therefore, when this heat treatment is carried out in stages, the thickness of the lamellae and its distribution according to the polymer chain structure can be quantitatively measured, and the distribution of the area of each melting peak can be measured accordingly.
[0114] According to the present invention, SSA can be performed in the following manner: polyethylene is heated to a first heating temperature of 140°C to 142°C using a differential scanning calorimeter, maintained (annealed) for 15 minutes to 30 minutes, and then cooled to 28°C to 32°C; while gradually reducing the heating temperature (wherein the n+1th heating temperature is set to be 3°C to 7°C lower than the nth heating temperature), the heating-annealing-cooling process is repeated until the final heating temperature reaches 50°C to 54°C.
[0115] More specifically, SSA can be performed by following the steps i) to v):
[0116] i) using a differential scanning calorimeter, the polyethylene was heated to 180°C and then held for 20 minutes to eliminate all thermal history before measurement;
[0117] ii) cooling from 180°C to 140°C and holding for 20 minutes, then cooling to 30°C and holding for 1 minute;
[0118] iii) heating to 135°C (5°C lower than 140°C) and holding for 20 minutes, then cooling to 30°C and holding for 1 minute;
[0119] iv) gradually reducing the heating temperature until the heating temperature reaches 50° C., wherein the n+1th heating temperature is 5° C. lower than the nth heating temperature, and the heating rate, holding time and cooling temperature are the same; and
[0120] v) Finally, the temperature was increased from 0°C to 180°C.
[0121] More specifically, polyethylene was first heated to 180°C using a differential scanning calorimeter (equipment name: DSC2500, manufacturer: TA Instruments) and held for 20 minutes to eliminate all thermal history of the sample before measurement. The temperature was then reduced from 180°C to 140°C and held for 20 minutes, then reduced to 30°C and held for 1 minute, and then raised again.
[0122] Next, the polyethylene was heated to a temperature (135°C) 5°C lower than the initial heating temperature of 140°C and maintained for 20 minutes, then the temperature was reduced to 30°C and maintained for 1 minute, and then the temperature was increased again. In this way, the n+1th heating temperature was 5°C lower than the nth heating temperature, while the holding time and cooling temperature were the same, and the heating temperature was gradually reduced until it reached 50°C. At this time, the heating rate and the cooling rate were controlled at 20°C / min, respectively. Finally, in order to quantitatively analyze the crystal distribution formed by repeated heating-annealing-cooling, the temperature was increased from 0°C to 180°C at a rate of 10°C / min, and the change in heat was observed and the thermogram was measured.
[0123] As described above, when the polyethylene of the present invention is heated after repeated heating-annealing-cooling using the SSA method, peaks of different temperatures appear, and accordingly, ethylene sequences of different thicknesses are obtained. Thus, the weighted average value (L) of the ethylene sequence is obtained using the following equations 4 and 5. w ) and the arithmetic mean (L n ):
[0124] [Equation 4]
[0125]
[0126] [Equation 5]
[0127]
[0128] In equations 4 and 5,
[0129] S i represents the area of each melting peak measured in the SSA thermogram, and
[0130] L i represents the average ethylene sequence length (ASL) corresponding to each melting peak in the SSA thermogram.
[0131] In addition, the ASL can be calculated from the measured SSA thermogram with reference to Journal of Polymer Science Part B: Polymer Physics 2002, Vol. 40, 813-821 and Journal of the Korean Chemical Society 2011, Vol. 55, No. 4.
[0132] L calculated in the same way as above w and L n The ratio (L w / L n) is the inhomogeneity (I) of the ethylene sequence. The larger the I value, the more uneven the distribution of the lamellae in the polymer chain and the higher the SCB content.
[0133] Specifically, when the polyethylene of the present invention is subjected to SSA analysis, the ethylene sequence heterogeneity (I) calculated according to the following equation 6 is 1.4 to 1.5, more specifically, 1.4 or more, or 1.43 or more, or 1.45 or more, and 1.5 or less, or 1.49 or less.
[0134] [Equation 6]
[0135] Inhomogeneity (I) = Lw / Ln
[0136] In equation 6,
[0137] Lw represents the weighted average value of ethylene sequence length (ESL) (unit: nm), and Ln represents the arithmetic mean value of ESL (unit: nm), which can be calculated by the above method.
[0138] Specifically, Lw may be 15 nm to 30 nm, and Ln may be 12 nm to 20 nm. More specifically, Lw is 15 nm or more, or 20 nm or more, or 21 nm or more, or 21.13 nm or more, and 30 nm or less, or 25 nm or less, or 22 nm or less, or 21.95 nm or less. In addition, Ln is 12 nm or more, or 14 nm or more, or 14.3 nm or more, or 14.32 nm or more, and 20 nm or less, or 16 nm or less, or 15.5 nm or less, or 15.2 nm or less, or 15.18 nm or less.
[0139] Since the polyethylene of the present invention has the heterogeneity within the above range, it can exhibit improved transparency and dart impact strength compared with the existing polyethylene of the same density due to the higher SCB content.
[0140] Furthermore, the ER (high MW polydispersity) of the polyethylene of the present invention is above 0.7, which is determined according to the following equation 7:
[0141] [Equation 7]
[0142] ER = C1G′ | at G″ref
[0143] In equation 7,
[0144] C1 represents the constant 1.781×10 -3 ,
[0145] G' represents the storage modulus of polyethylene (dyne / cm 2),as well as
[0146] G" represents the loss modulus of polyethylene 5000dyne / cm 2 .
[0147] ER (polydispersity at high MW), also known as rheological polydispersity, is derived by measuring the rheological properties (or rheological properties) of a polymer melt. The rheological properties of a polymer melt depend strongly on the basic molecular structure, in particular the molecular weight, molecular weight distribution and long chain branching (LCB). ER is independent of the molecular weight and molecular weight distribution of polyethylene, but rather quantifies the polydispersity at high Mw.
[0148] The larger the ER value, the higher the polydispersity at high Mw, and the presence of molecules with long relaxation time. Conversely, the smaller the ER value, the less polydispersity at high Mw, and the presence of molecules with short relaxation time. The polyethylene of the present invention meets the ER requirements within the above range, thereby being able to exhibit excellent transparency and processing characteristics. More specifically, ER is 0.7 or more, or 0.75 or more, or 0.76 or more, and 0.9 or less, or 0.86 or less.
[0149] ER can be calculated by the method disclosed in “New measures of polydispersity from rheological data on polymer melts”, Journal of Applied Polymer Science, Vol. 57, 1605-1626 (1995).
[0150] The ER measurement method and conditions of the present invention are described in the following experimental examples.
[0151] Furthermore, the polyethylene of the present invention has a PDR (Overall Polydispersity) of 5.0 or more, which is determined according to the following Equation 8:
[0152] [Equation 8]
[0153]
[0154] In Equation 8, η*1, η*2, and η*3 represent the reference complex modulus G * ref1 , G * ref2 and G * ref3 In the present invention, based on the linear polymer G * ref1 =1.95×10 4 dyn / cm2 , G * ref2 =(G * ref1 G * ref3 ) 1 / 2 , and log10(G * ref3 / G * ref1 )=2, obtain eta*1, eta*2 and eta*3.
[0155] ER does not reflect the contribution of low Mw. Therefore, when the overall polydispersity is of interest, i.e., when both high MW and low MW contributions are of interest, the complex modulus (G * )Function PDR.
[0156] PDR represents the overall polydispersity of polyethylene, in Equation 8, represents the shear sensitivity, Indicates the curvature of the viscosity curve. A higher PDR means a higher shear sensitivity, a higher polydispersity, and therefore better processing performance. Conversely, a lower PDR means a lower shear sensitivity, a lower polydispersity, and therefore worse processing performance.
[0157] Since the polyethylene of the present invention exhibits a PDR in the above range, it can exhibit excellent processability. More specifically, the PDR is 5.0 or more, or 5.5 or more, or 5.7 or more, or 6.0 or more, and 7 or less, or 6.9 or less, or 6.5 or less.
[0158] The PDR measurement method and conditions of the present invention are described in the following experimental examples.
[0159] Furthermore, the head pressure of the polyethylene of the present invention is 210 bar to 260 bar, more specifically, 210 bar or more, or 220 bar or more, or 222 bar or more, and 260 bar or less, or 255 bar or less, or 251 bar or less.
[0160] In addition, the output index (Output Index) of the polyethylene calculated according to the following equation 9 is 1.60 g / (min·bar) or more. More specifically, the output index is 1.60 g / (min·bar) or more, or 1.62 g / (min·bar) or more, or 1.64 g / (min·bar) or more, and 2 g / (min·bar) or less, or 1.9 g / (min·bar) or less, or 1.85 g / (min·bar) or less.
[0161] [Equation 9]
[0162] Output index = blow molding extruder 1 minute output (g / min) / head pressure (bar)
[0163] The measurement method and conditions of the head pressure and output of the present invention are as described in the following experimental examples.
[0164] In addition, according to ASTM D1505, the density of the polyethylene of the present invention is 0.916 g / cm 3 Up to 0.920g / cm 3 .
[0165] When the density of polyethylene is less than 0.916 g / cm 3 In addition, there is a restrictive relationship between density and dart impact strength. When the density of polyethylene is greater than 0.920 g / cm 3 When the dart impact strength is reduced, it is difficult to reduce the thickness during the film production process. More specifically, the polyethylene density of the present invention is 0.916 g / cm 3 Above or 0.918g / cm 3 Above, and 0.920g / cm 3 Below or 0.919g / cm 3 the following.
[0166] In addition, the melt index (MI) of polyethylene was measured according to ASTM D1238 at a temperature of 190°C and a load of 2.16 kg. 2.16 ) is 0.5 g / 10 min to 1.5 g / 10 min, more specifically, 0.5 g / 10 min or more or 0.8 g / 10 min or more, and 1.2 g / 10 min or less or 1.0 g / 10 min or less.
[0167] Due to its low density, optimal melt index range and the above physical properties, polyethylene can exhibit excellent processing performance and high dart drop impact strength.
[0168] The polyethylene of the present invention may be an ethylene homopolymer consisting of ethylene repeating units derived from ethylene monomers only; or an ethylene / α-olefin copolymer comprising α-olefin repeating units derived from α-olefin monomers and ethylene repeating units.
[0169] Specific examples of the α-olefin monomer may include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, and the like, and two or more thereof may be used.
[0170] More specifically, the polyethylene of the present invention is an ethylene / 1-hexene copolymer.
[0171] Meanwhile, the polyethylene having the above-mentioned physical properties can be prepared by the following preparation method, which comprises the following steps: based on the total weight of monomers comprising ethylene and olefin monomers, in the presence of a hybrid supported catalyst (comprising a first transition metal compound represented by the following Chemical Formula 1 and a second transition metal compound represented by the following Chemical Formula 2), while introducing 5 ppm to 30 ppm of hydrogen, slurry polymerization of ethylene and olefin monomers.
[0172] [Chemical formula 1]
[0173]
[0174] In Chemical Formula 1,
[0175] M1 is a Group 4 transition metal;
[0176] A1 is C, Si or Ge,
[0177] R 11 and R 11 'Each independently is C 6-20 Aryl, C 7-20 Alkyl aryl, C 7-20 Arylalkyl or C 7-20 Alkoxyalkyl,
[0178] R 12 , R 13 , R 14 , R 12 '、R 13 ' and R 14 'are each independently hydrogen, halogen, C 1-20 Alkyl, C 1-20 Alkenyl, C 1-20 Alkoxy, C 6-20 Aryl, C 7-20 Alkyl aryl or C 7-20 Arylalkyl,
[0179] R 15 and R 16 One of them is C 2-20 Alkoxyalkyl, the other is C 1-20 Alkyl, and
[0180] X 11 and X 12 are independently halogen or C 1-20 alkyl,
[0181] [Chemical formula 2]
[0182]
[0183] In chemical formula 2,
[0184] M2 is a Group 4 transition metal;
[0185] A2 is C, Si or Ge,
[0186] R 21 To R 24 Each independently is C 1-20 alkyl,
[0187] R 25 C 1-20 alkyl,
[0188] R 26 For C 1-20 Alkyl-substituted or unsubstituted C 6-20 Aryl,
[0189] R 27 To R 29 are independently hydrogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 6-20 Aryl, C 7-20 Alkyl aryl, C 7-20 Any of arylalkyl, or R 27 To R 29 Two adjacent groups are connected to form C 4-8 Aliphatic ring,
[0190] R 31 and R 32 Each independently is C 1-20 Alkyl, and
[0191] X 21 and X 22 are independently halogen or C 1-20 alkyl.
[0192] In the present invention, substituents of the chemical formulae will be described in detail hereinafter.
[0193] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).
[0194] C 1-20 The alkyl group may be a linear alkyl group, a branched alkyl group, or a cycloalkyl group. 1-20 Alkyl can be C 1-20 Straight chain alkyl; C 1-10 Straight chain alkyl; C 1-5 Straight chain alkyl; C 3-20 Branched alkyl or ring; C 3-15Branched alkyl or cycloalkyl; or C 3-10 More specifically, C 1-20 The alkyl group may include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, cyclohexyl, and the like.
[0195] C 2-20 The alkenyl group may be a straight chain alkenyl group, a branched chain alkenyl group or a cycloalkenyl group. 2-20 The alkenyl group can be C 2-20 Straight chain alkenyl, C 2-10 Straight chain alkenyl, C 2-5 Straight chain alkenyl, C 3-20 Branched alkenyl, C 3-15 Branched alkenyl, C 3-10 Branched alkenyl, C 5-20 Cycloalkenyl or C 5-10 More specifically, C 2-20 The alkenyl group may be ethenyl, propenyl, butenyl, pentenyl or cyclohexenyl, etc.
[0196] C 1-20 The alkoxy group may be a straight chain, branched chain or cycloalkoxy group. 1-20 Alkoxy can C 1-20 Straight chain alkoxy; C 1-10 Straight chain alkoxy; C 1-5 Straight chain alkoxy; C 3-20 Branched alkoxy or cycloalkoxy; C 3-15 Branched alkoxy or cycloalkoxy; or C 3-10 More specifically, C 1-20 The alkoxy group may be methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentyloxy, neopentyloxy or cyclohexyloxy, or the like.
[0197] C 2-20 Alkoxyalkyl includes -R y -OR z structure, which can be an alkyl group (-R y ) is replaced by one or more hydrogen atoms of an alkoxy group (-OR z ) substituted substituent. More specifically, C 2-20 The alkoxyalkyl group may be methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl or the like.
[0198] C 6-20 Aryl may refer to monocyclic, bicyclic or tricyclic aromatic hydrocarbons. 6-20 Aryl may be phenyl, naphthyl or anthracenyl, etc.
[0199] C 7-20 Alkylaryl may refer to a substituent in which one or more hydrogen atoms in an aryl group are replaced by an alkyl group. 7-20 The alkylaryl group may be methylphenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, n-butylphenyl, isobutylphenyl, tert-butylphenyl, cyclohexylphenyl, or the like.
[0200] C 7-20 Arylalkyl may refer to a substituent in which one or more hydrogen atoms of an alkyl group are replaced by an aryl group. 7-20 Arylalkyl may be benzyl, phenylpropyl or phenylhexyl, and the like.
[0201] In addition, the Group 4 transition metal may be titanium, zirconium, hafnium or the like.
[0202] The hybrid metallocene catalyst of the present invention may be a hybrid catalyst comprising a first transition metal compound with a high molecular weight and high copolymerizability and a second transition metal compound with a low molecular weight and low copolymerizability.
[0203] Specifically, the first transition metal compound represented by Chemical Formula 1 helps prepare a high molecular weight copolymer having a high SCB content, and the second transition metal oxide represented by Chemical Formula 2 helps prepare a low molecular weight copolymer having a low SCB (short chain branch) content.
[0204] Therefore, the hybrid metallocene catalyst of the present invention exhibits high copolymerizability to polyethylene in the high molecular weight region due to the effect of the first transition metal compound, and exhibits low copolymerizability to polyethylene in the low molecular weight region due to the effect of the second transition metal compound. Therefore, the polyethylene prepared using the hybrid metallocene catalyst of the present invention has a suitable crystallinity and a uniform lamellar structure. In addition, since the lamellar structure has a structure connected by connecting chains, it can exhibit a higher dart drop impact strength. In other words, in order to improve the dart drop impact strength, it is necessary to have a sufficiently low crystallinity so that the high molecular weight chains that can become connecting chains are dispersed into the non-crystalline region.
[0205] The first transition metal compound facilitates the preparation of high molecular weight copolymers and exhibits relatively high comonomer incorporation rates compared to the second transition metal compound.
[0206] In particular, since the first transition metal compound asymmetrically contains two indenyl derivatives with different structures, and the two indenyl derivatives are connected by a bridge group, it has high structural stability and can show high polymerization activity even when loaded on a carrier.
[0207] In addition, since the carbon 4 of each indenyl derivative is substituted by a bulky group, such as C 1-20 Alkyl substituted C 6-20Aryl groups can therefore maintain high activity by creating an appropriate electronic environment.
[0208] In addition, methyl and isopropyl substituents were introduced at the 2-carbon of each indenyl derivative, and OtBu, which can coordinate with MAO, was located on the bridge connecting the two indenyl ligands, thereby ensuring stable activity through a high loading rate. As a result, polyethylene with excellent processing performance and mechanical properties during olefin polymerization, as well as high activity and excellent morphology, can be prepared.
[0209] Specifically, in Formula 1, the central metal (M1) may be specifically a Group 4 transition metal Ti, Zr or Hf, more specifically Zr.
[0210] In addition, in Formula 1, A1 may specifically be Si.
[0211] In addition, R 11 and R 11 ' can be independently C 6-12 Aryl, C 7-18 Alkyl aryl, C 7-18 Alkoxyalkyl is more particularly phenyl, naphthyl, tert-butylphenyl, 3,5-di-tert-butylphenyl, 2,5-dimethylphenyl or methoxyphenyl.
[0212] In addition, R 12 , R 13 , R 14 , R 12 '、R 13 ' and R 14 ' may each be hydrogen.
[0213] In addition, R 15 and R 16 One of them can be C 2-12 Alkoxyalkyl, the other may be C 1-8 Alkyl, more specifically, R 15 and R 16 One of the groups may be tert-butoxyhexyl and the other may be methyl.
[0214] In addition, X 11 and X 12 can be independently chlorine or methyl, more specifically, X 11 and X 12 Each may be chlorine.
[0215] Therefore, the first transition metal compound can be specifically the following compound, wherein in Formula 1, M1 is Ti, Zr, or Hf, A1 is Si, R 11 and R 11 'Each independently is C 6-12 Aryl, C 7-18Alkyl aryl or C 7-18 Alkoxyaryl, R 12 , R 13 , R 14 , R 12 '、R 13 ' and R 14 are independently hydrogen, R 15 and R 16 One of them is C 2-12 Alkoxyalkyl, the other is C 1-8 Alkyl, X 11 and X 12 Each may independently be chlorine or methyl.
[0216] More specifically, the first transition metal compound may be the following compound, wherein in Formula 1, M1 is Zr, A1 is Si, R 11 and R 11 ' are each independently phenyl, naphthyl, tert-butylphenyl, 3,5-di-tert-butylphenyl, 2,5-dimethylphenyl or methoxyphenyl, R 12 , R 13 , R 14 , R 12 '、R 13 ' and R 14 ' are each independently hydrogen, R 15 and R 16 One of them is tert-butyloxyhexyl, the other is methyl, X 11 and X 12 are each independently chlorine.
[0217] More specifically, the first transition metal compound may be any one selected from the group consisting of the following compounds:
[0218]
[0219] The first transition metal compound represented by Formula 1 can be synthesized by using known reactions. For more detailed synthesis methods, please refer to the synthesis examples.
[0220] Meanwhile, the second transition metal compound represented by Formula 2 facilitates the preparation of a low molecular weight copolymer and exhibits a relatively low copolymer incorporation rate compared to the first transition metal compound.
[0221] Specifically, in Formula 2, M2 may be Ti, Zr or Hf, more specifically Zr or Hf.
[0222] In addition, A2 can be specifically Si.
[0223] In addition, R 21 To R 24 Can be independently C 1-8Alkyl, more specifically, R 21 To R 24 Each may be a methyl group.
[0224] In addition, R 25 Can be C 1-8 Alkyl, more specifically, R 25 It may be methyl.
[0225] In addition, R 26 Can be C 1-8 Alkyl substituted or unsubstituted C 6-18 Aryl, more specifically, R 26 It may be phenyl, tert-butylphenyl, naphthyl or 2,5-dimethylphenyl.
[0226] In addition, R 27 To R 29 are each independently hydrogen, or R 27 To R 29 Two adjacent groups are connected to form C 4-8 aliphatic ring, more specifically, R 27 To R 29 are each independently hydrogen, or R 27 To R 29 Two adjacent groups are connected to each other to form a cyclopentyl or cyclohexyl ring.
[0227] In addition, R 31 and R 32 Can be independently C 1-8 Alkyl, more specifically, R 31 and R 32 Each may be a methyl group.
[0228] In addition, X 31 and X 32 Each may independently be chlorine or methyl, more specifically chlorine.
[0229] Therefore, the second transition metal compound can be the following compound, wherein in Formula 2, M2 is Ti, Zr or Hf, A2 is Si, R 21 To R 24 Each independently is C 1-8 Alkyl, R 25 C 1-8 Alkyl, R 26 For C 1-8 Alkyl substituted or unsubstituted C 6-18 Aryl, R 27 To R 29 are each independently hydrogen, or R 27 To R 29 Two adjacent groups are connected to form C 4-8 Aliphatic ring, R31 and R 32 Each independently is C 1-8 Alkyl, and X 31 and X 32 Each is independently chloro or methyl.
[0230] More specifically, the second transition metal compound may be the following compound, wherein, in Formula 2, M2 is Zr or Hf, A2 is Si, R 21 To R 24 are each independently methyl, R 25 is methyl, R 26 is phenyl, tert-butylphenyl, naphthyl or 2,5-dimethylphenyl, R 27 To R 29 are each independently hydrogen, or R 27 To R 29 Two adjacent groups are connected to form a cyclopentyl or cyclohexyl ring, R 31 and R 32 are each independently methyl, and X 31 and X 32 are each independently chlorine.
[0231] More specifically, the second transition metal compound represented by Formula 2 may be any one selected from the group consisting of the following compounds:
[0232]
[0233] The second transition metal compound represented by Formula 2 can be synthesized by using known reactions. For more detailed synthesis methods, please refer to the synthesis examples.
[0234] In the case of a hybrid metallocene catalyst, the first transition metal has only a racemic isomer. In contrast, the second transition metal compound has neither a meso isomer nor a racemic isomer.
[0235] As used herein, the term "racemic form", "racemate" or "racemic isomer" means that the same substituents on the two ligands are located on opposite sides of the plane containing the center of the Group 4 transition metal (such as a transition metal such as zirconium (Zr) or hafnium (Hf)) represented by M1 in Formula 1 and the ligand portion.
[0236] In addition, as used herein, the term "racemic form" or "mesomer" is a stereoisomer of the above-mentioned racemic isomer, which means that the same substituents of the two ligands are located on the same side of the plane containing the Group 4 transition metal represented by M1 in Formula 1 and the center of the ligand portion.
[0237] In addition, the hybrid metallocene catalyst of the present invention can improve the catalytic activity by controlling the molar ratio of the first transition metal compound to the second transition metal compound, and further improve the physical properties of the prepared polymer.
[0238] For example, the hybrid metallocene catalyst may contain a first transition metal compound and a second transition metal compound in a molar ratio of 1:6 to 6:1. Under the condition that the above-mentioned mixing ratio requirements are met, while maintaining excellent catalytic activity, the crystal structure of the polyethylene prepared by the hybrid supported catalyst is further optimized, and the distribution of the lamellar structure is more uniform, thereby further improving the dart impact strength and processing performance. More specifically, the molar ratio of the first transition metal compound to the second transition metal compound is 2:1 to 4:1, or 2:1 to 3:1.
[0239] In addition, the hybrid metallocene catalyst of the present invention may further comprise one or more supports and co-catalysts.
[0240] When the hybrid metallocene catalyst includes a support, the first transition metal compound and the second transition metal compound are used in the form of a supported catalyst supported on the support.
[0241] As the carrier, a carrier having a highly reactive hydroxyl group, silanol group or siloxane group on the surface can be used. For this purpose, a carrier surface-modified by removing surface moisture by calcination or drying can be used.
[0242] For example, silica prepared by calcining silica gel, silica, silica-alumina, silica-magnesia, etc., such as high temperature dried silica, can be used. These supports may typically contain oxides, carbonates, sulfates, and nitrates, such as Na2O, K2CO3, BaSO4, and Mg(NO3)2, etc.
[0243] When used as a supported catalyst, the prepared polymer has excellent particle shape and bulk density, and the catalyst can be appropriately used in conventional slurry polymerization, bulk polymerization and gas phase polymerization processes. In addition, among various carriers, the silica carrier supports the transition metal compound through the chemical combination of its functional groups, so that in the ethylene polymerization process, the catalyst released from the carrier surface is very small, so when polyethylene is prepared by slurry polymerization or gas phase polymerization, the fouling phenomenon of adhering to the reactor wall or itself can be minimized.
[0244] The average particle size (D50) of the carrier is 20 μm to 40 μm. When the carrier has the above particle size, it can load the transition metal compound with higher efficiency, thereby improving the catalytic activity. More specifically, the average particle size can be 20 μm or more, or 25 μm or more, and 40 μm or less, or 30 μm or less.
[0245] Meanwhile, in the present invention, the average particle size (D50) of the carrier refers to the particle size at which the cumulative number of particles of the particle size (particle size) is distributed at 50%. D50 can be measured using a laser diffraction method. Specifically, the carrier to be measured can be dispersed in a dispersion medium such as deionized water, and then placed in a laser diffraction particle size analyzer (e.g., Microtrac S3500). When the particles pass through the laser beam, the difference in the diffraction pattern relative to the particle size is calculated, thereby calculating the particle size distribution. The average particle size can be determined by calculating the particle size at 50% of the cumulative number of particles distributed in the measuring device.
[0246] In addition, when loaded on a silica carrier, the loading amounts of the first transition metal compound and the second transition metal compound can be respectively 1 mmol or more, or 10 mmol or more, or 15 mmol or more, or 17.5 mmol or more, and 100 mmol or less, or 80 mmol or less, or 60 mmol or less, or 52.5 mmol or less based on 1000 g of silica. When loaded within the above content range, the supported catalyst exhibits appropriate activity, which is advantageous in maintaining catalytic activity and economic efficiency.
[0247] Furthermore, the hybrid metallocene catalyst may further comprise a cocatalyst in order to improve high activity and process stability.
[0248] Specifically, the co-catalyst may include one or more of the compounds represented by Formula 3 below.
[0249] [Chemical formula 3]
[0250] -[Al(R 41 )-O]a-
[0251] In chemical formula 3,
[0252] R 41 is halogen; or an unsubstituted C substituted by a halogen 1-20 Hydrocarbyl; and
[0253] a is an integer greater than or equal to 2.
[0254] Meanwhile, in the present specification, a hydrocarbon group is a monovalent functional group formed by removing a hydrogen atom from a hydrocarbon, and may include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, an alkyl group, an alkynyl group, an alkaryl group, an alkenaryl group, an alkynaryl group, etc. In addition, the hydrocarbon group having 1 to 20 carbon atoms may be a hydrocarbon group having 1 to 15 carbon atoms or a hydrocarbon group having 1 to 10 carbon atoms. Specifically, the hydrocarbon group having 1 to 20 carbon atoms may be a linear, branched or cyclic alkyl group, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, a cyclohexyl group, etc.; or an aryl group, such as a phenyl group, a naphthyl group, an anthracenyl group, etc.
[0255] The compound represented by Formula 3 may include an alkylaluminoxane-based compound such as methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, or butylaluminoxane, and any one of them or a mixture of two or more thereof may be used.
[0256] Among the above mentioned compounds, the cocatalyst may more particularly be an alkylaluminoxane-based cocatalyst, for example methylaluminoxane.
[0257] The alkylaluminoxane-based cocatalyst stabilizes the first transition metal compound and the second transition metal compound and acts as a Lewis acid, thereby further enhancing the catalytic activity by including a metal element capable of forming a bond with a functional group introduced into the bridge group of the first transition metal compound and the second transition metal compound through Lewis acid-base interaction.
[0258] In addition, the amount of the co-catalyst can be appropriately adjusted according to the physical properties or effects of the catalyst and polyethylene. For example, when using silica as a carrier, based on the weight of the carrier, for example, 1000g of silica, the loading amount of the co-catalyst can be more than 100g, or more than 1000g, or more than 2000g, and less than 6000g, or less than 5500g, or less than 5400g.
[0259] The hybrid metallocene catalyst of the present invention having the above structure can be prepared by the following preparation method, which includes: the step of loading a co-catalyst compound on a carrier, the step of loading a first transition metal compound and a second transition metal compound on a carrier, wherein the loading order of the co-catalyst and the first transition metal compound and the second transition metal compound can be changed as required, and the loading order of the first transition metal compound and the second transition metal compound can also be changed as required. The first transition metal compound and the second transition metal compound can be loaded at the same time. Considering the effect of the loaded catalyst of the structure determined according to the loading order, after loading the co-catalyst on the carrier, the first transition metal compound and the second transition metal compound are loaded in sequence, ensuring that the prepared loaded catalyst has higher catalytic activity and excellent process stability in the polyethylene preparation process.
[0260] As described above, the hybrid metallocene catalyst of the present invention can exhibit excellent catalytic activity by comprising a first transition metal compound and a second transition metal compound having specific structures. Therefore, the hybrid metallocene catalyst can be applied to the polymerization of olefin monomers.
[0261] Meanwhile, the olefin monomer may be ethylene, α-olefin, cyclic olefin, diene olefin, or triene olefin having two or more double bonds.
[0262] Specific examples of olefin monomers include ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, norbornene, norbornadiene, ethylidene norbornene, phenyl norbornene, vinyl norbornene, dicyclopentadiene, 1,4-butadiene, 1,5-pentadiene, 1,6-hexadiene, styrene, α-methylstyrene, divinylbenzene, 3-chloromethylstyrene, etc., and two or more of these monomers may be mixed and copolymerized. More specifically, the olefin monomer may be 1-hexene.
[0263] The amount of olefin monomer added can be determined according to the physical properties of the polyethylene to be prepared. For example, considering the physical properties of the polyethylene to be achieved in the present invention and the effects of improving high dart impact strength and processing performance, the amount of olefin monomer introduced can be 4 wt % to 15 wt %, more specifically, 4 wt % or more, or 5 wt % or more, or 5.5 wt % or more, and 15 wt % or less, or 14.8 wt % or less, or 14.6 wt % or less, based on the total weight of the monomers including the ethylene monomer and the olefin monomer.
[0264] The polymerization reaction was carried out under the condition of hydrogen input.
[0265] Specifically, the amount of hydrogen introduced is 5 ppm to 30 ppm based on the total weight of the ethylene monomer, or when the monomer contains an olefin monomer in addition to ethylene, based on the total weight of the monomers including ethylene and the olefin monomer. More specifically, the amount of hydrogen introduced can be 5 ppm or more, or 10 ppm or more, or 15 ppm or more, or 16 ppm or more, and 30 ppm or less, or 28 ppm or less, or 25 ppm or less, or 24 ppm or less, based on the total weight of the monomer.
[0266] When introduced in the above range, the above physical properties of polyethylene are more easily achieved.
[0267] The polymerization may be carried out by slurry polymerization.
[0268] Thus, the polymerization reaction may be carried out using a single continuous slurry polymerization reactor or a loop slurry polymerization reactor.
[0269] In addition, the hybrid supported catalyst can be injected in aliphatic hydrocarbon solvents having 4 to 12 carbon atoms, such as isobutane, pentane, hexane, heptane, nonane, decane and isomers thereof, aromatic hydrocarbon solvents, such as toluene, benzene, or hydrocarbon solvents substituted with chlorine atoms, such as dichloromethane or chlorobenzene, etc. The solvent used here is preferably treated with a small amount of alkyl aluminum to remove a small amount of water or air, because water or air can act as catalyst poisons. A cocatalyst may further be used.
[0270] In addition, the polymerization reaction can be carried out at a temperature of 40°C or more, or 60°C or more, or 80°C or more and 110°C or less, 100°C or less, or 90°C or less. In addition, when the pressure conditions during the polymerization reaction are further controlled, the reaction can be carried out at a pressure of 5 bar or more, 10 bar or more, 20 bar or more and 50 bar or less, 45 bar or less, or 40 bar or less. When the polymerization is carried out at such a temperature and pressure, it is easier to achieve the physical properties required of polyethylene.
[0271] The polyethylene prepared by the above preparation method has a uniformly distributed lamellar structure and appropriate crystallinity. Therefore, this polyethylene exhibits excellent dart impact strength characteristics and transparency. Therefore, this polyethylene can be used to produce films, specifically blown films that require high mechanical properties and excellent transparency.
[0272] Thus, the present invention provides a resin composition comprising polyethylene, in particular, a composition for producing a film.
[0273] In addition, the present invention also provides a film, specifically a blown film made of polyethylene or the resin composition.
[0274] Except using polyethylene, film of the present invention can be produced according to conventional film production method.For example, can be by polyethylene and optional additive (for example antioxidant and processing aid) are mixed to prepare the composition for producing film, and use forcing machine that composition is extruded into film, thereby manufacture film.
[0275] Furthermore, by including polyethylene, the film can express excellent transparency and mechanical properties.
[0276] Specifically, according to method A of ASTM D 1709, the dart impact strength of the film is measured under the conditions of a blow-up ratio (BUR) of 2.3 to 3 (specifically, a BUR of 2.5) and a film thickness of 45 μm to 55 μm (specifically, a film thickness of 50 μm), and the haze of the film is measured according to ISO 13468 standard. It is 14% or less or 13.5% or less. Since the higher the dart impact strength, the better the film, there is no particular restriction on the upper limit. However, the dart impact strength can be, for example, 3000 gf or less. In addition, the lower the haze, the better the film, so the lower limit is not particularly limited either. However, the haze can be, for example, 1% or more.
[0277] Hereinafter, preferred exemplary embodiments will be provided to better understand the present invention. However, the following exemplary embodiments are provided only to more easily understand the present invention, but the content of the present invention is not limited thereto.
[0278] Meanwhile, in this specification, room temperature refers to 23±5°C.
[0279] Preparation of transition metal compounds
[0280] Synthesis example 1
[0281] 2-Methyl-4-naphthyl-indene (1 equivalent) was dissolved in MTBE (0.3 M), and n-BuLi (1.05 equivalent) was slowly added dropwise at -25°C, followed by stirring at room temperature for 3 hours. To the resulting product, (t-BuOHex)MeSiCl2 (1.05 equivalent) was added at -10°C, and stirred at room temperature overnight to prepare a solution containing a monosilicon compound.
[0282] In another stirrer, 2-isopropyl-4-phenyl-indene (1 equivalent) was dissolved in MTBE (0.3M), and n-BuLi (1.05 equivalent) was slowly added dropwise at -25°C, followed by stirring at room temperature for 3 hours. CuCN (2 mol%) was added to the resulting product, stirred for 30 minutes, and then the solution containing the monosilicon compound (a1) prepared above was introduced, stirred at room temperature overnight, then treated with water and dried. Thus, ligand (a2) was obtained.
[0283] The ligand (a2) was dissolved in toluene / ethyl ether (volume ratio 2 / 1, 0.53 M), n-BuLi (2.05 equivalents) was introduced into the resulting solution at -25°C, and then stirred at room temperature for 5 hours to prepare a lithiated ligand.
[0284] ZrCl4 (1 equivalent) and toluene (0.17M) are mixed in another flask to prepare slurry, and then the slurry is introduced into the lithiated ligand, and stirred at room temperature overnight. After the reaction is completed, the vacuum drying solvent is introduced into the dried product with DCM, and the LiCl is removed by filtration. The filtrate is dried under vacuum, DCM and hexane are added, and recrystallized at room temperature. Then, the solid generated is filtered and vacuum dried to obtain a solid phase transition metal compound (A-1).
[0285] 1 H NMR(500MHz, CDCl3,7.26ppm):0.82(1.5H,t),1.01(3.5H,m),1.14(9H,s),1.40(9H,s),1.52(8H,m),1.65(4H,m),1.77(2H,m),2.21(3H,s ),3.25(1H,m),3.33(2H,t),6.58(1H,s),6.94(1H,s),7.15(1H,t),7.28(5H,m),7.40(4H,m),7.44(3H,m),7.63(2.5H,m),7.82((2.5H,d)
[0286]
[0287] Synthesis example 2
[0288] The following transition metal compound (A-2) was prepared in the same manner as in Synthesis Example 1 except that 2-methyl-4-(3,5-di-tert-butylphenyl)indene was used instead of 2-methyl-4-naphthyl-indene.
[0289] 1 H NMR(500MHz, CDCl3,7.26ppm):0.85(5H,m),1.15(9H,s),1.32(20H,s,m),1.42(8H,m),1.59(2H,m),1.83(2H,m),2.22(3H,s),3.27(1H,m),3.37 (2H,t),6.75(1H,s),6.87(1H,s),7.12(2H,m),7.30(1H,m),7.42(2H,m) ,7.46(3H,m),7.56(1H,m),7.60(s,1H),7.70(2.5H,m),7.74(1.5H,s,d)
[0290]
[0291] Synthesis example 3
[0292] The following transition metal compound (A-3) was prepared in the same manner as in Synthesis Example 1, except that 2-methyl-4-(4-tert-butylphenyl)-indene was used instead of 2-methyl-4-naphthyl-indene, and 2-isopropyl-4-(4-tert-butylphenyl)-indene was used instead of 2-isopropyl-4-phenyl-indene.
[0293] 1 H NMR(500MHz, CDCl3,7.26ppm):0.89(3H,t),1.08(2H,m),1.20(9H,s),1.35(24H,s,m),1.51(2H,m),1.61(2H,m),1.66(2H,m),1.88(2H,m),2.25( 3H,s),3.28(1H,m),3.38(2H,t),6.98(1H,s),7.02(1H,s),7.11(2H,dq) ,7.36(2H,dd),7.46(4H,dd),7.51(1H,m),7.60(4.5H,m),7.70(0.5H,d)
[0294]
[0295] Synthesis example 4
[0296]
[0297] 1 equivalent of tetramethylcyclopentadiene (TMCP) was dissolved in THF (0.3 M), 1.05 equivalents of n-BuLi was slowly added dropwise at -25°C, and then stirred at room temperature for 3 hours. Me2SiCl2 (1.05 equivalents) was added to the resulting reaction solution at -10°C, and stirred at room temperature overnight to prepare a solution containing the monosilicon compound (b1).
[0298] In another reactor, 2-methyl-4-phenyl-indene (1 equivalent) was dissolved in MTBE (0.3 M), and n-BuLi (1.05 equivalent) was slowly added dropwise at -25°C, followed by stirring at room temperature for 3 hours. CuCN (2 mol%) was added to the resulting reaction solution, stirred for 30 minutes, and then the solution containing the monosilicon compound (b1) prepared above was introduced, stirred at room temperature overnight, then treated with water and dried. Thus, ligand (b2) was obtained.
[0299] The ligand (b2) was dissolved in toluene / ethyl ether (volume ratio of 2 / 1, 0.53 M), n-BuLi (2.05 equivalents) was added to the resulting solution at -25°C, and then stirred at room temperature for 5 hours to prepare the lithiated ligand.
[0300] ZrCl4 (1 equivalent) and toluene (0.17M) are mixed in another flask to prepare slurry, and then the slurry is introduced into the lithiated ligand, and stirred at room temperature overnight. After the reaction is completed, the solvent is removed by vacuum drying, DCM is introduced into the dried product, and LiCl is removed by filtration. The filtrate is dried under vacuum, DCM and hexane are added, and recrystallized at room temperature. Then, the solid generated is filtered, and vacuum drying is performed to obtain a solid phase transition metal compound (B-1).
[0301] 1 H NMR(500MHz, CDCl3,7.26ppm):1.12(3H,s),1.23(3H,s),1.88(3H,s),1.93(3H,s),1.99(3H,s),2.06(3H, s),2.28(3H,s),7.02(1H,s),7.11(1H,m),7.29(1H,d),7.40(1H,m),7.46(2H,t),7.60(1H,d),7.68(2H,d)
[0302] Synthesis example 5
[0303] The following transition metal compound (B-2) was prepared in the same manner as in Synthesis Example 4 except that 2-methyl-4-(4-tert-butylphenyl)indene was used instead of 2-methyl-4-phenyl-indene.
[0304] 1 H NMR(500MHz, CDCl3,7.26ppm):1.11(9H,s),1.22(3H,s),1.38(9H,s),1.88(6H,d),1.9 9(3H,s),2.02(3H,m),2.33(3H,s),7.08(1H,s),7.12(2H,m),7.28(2H,d),7.58(3H,d)
[0305]
[0306] Synthesis example 6
[0307] The following transition metal compound (B-3) was prepared in the same manner as in Synthesis Example 4 except that 2-methyl-4-(2,5-dimethylphenyl)indene was used instead of 2-methyl-4-phenyl-indene.
[0308] 1 H NMR(500MHz, CDCl3,7.26ppm):0.96(6H,s),1.77(6H,s),2.18(6H,m),1.57(3H,s),1.7 9(3H,s),2.22(3H,s),6.89(1H,s),7.20(1H,m),7.36(2H,m),7.57(2H,m),7.70(1H,s)
[0309]
[0310] Synthesis Example 7
[0311] A transition metal compound (C-1) having the following structure was prepared in the same manner as in Comparative Synthesis Example 2 of Korean Patent Publication No. 10-2022-0067494.
[0312]
[0313] Synthesis example 8
[0314] A transition metal compound (C-2) having the following structure was prepared in the same manner as in Comparative Synthesis Example 3 of Korean Patent Publication No. 10-2022-0067494.
[0315]
[0316] Synthesis example 9
[0317] A transition metal compound (C-3) having the following structure was prepared in the same manner as Preparation Example 1 of Korean Patent Publication No. 10-2016-0067508.
[0318]
[0319] Preparation of hybrid metallocene catalysts
[0320] Preparation Example 1
[0321] 2.0 kg of toluene and 1000 g of silica (SP2410, manufactured by Grace Davision) were placed in a 20 Lsus high pressure reactor and the reactor temperature was raised to 40°C while stirring. 5.4 kg of methylaluminoxane (10% by weight in toluene, manufactured by Albemarle) was placed in the reactor, heated to 70°C, and stirred at about 200 rpm for about 12 hours. Then, the temperature of the reactor was reduced to 40°C and stirring was stopped. The reaction product was allowed to stand for about 10 minutes and then decanted. 2.0 kg of toluene was added to the reaction product, stirred for about 10 minutes, stirring was stopped, and the mixture was allowed to stand for about 30 minutes and then decanted.
[0322] 2.0 kg of toluene was added to the reactor, and then the compound (A-1) (52.5 mmol) as the first transition metal compound prepared in Synthesis Example 1 and the compound (B-1) (17.5 mmol) as the second transition metal compound prepared in Synthesis Example 4 and 1000 mL of toluene were added. The temperature of the reactor was raised to 85° C., and the reaction mixture was stirred for about 90 minutes.
[0323] Then, the temperature of the reactor was lowered to room temperature, stirring was stopped, the reaction product was allowed to stand for about 30 minutes, and then the reaction product was decanted. Subsequently, 3 kg of hexane was introduced into the reactor, the hexane slurry solution was transferred to a 20 L filter dryer to filter the solution, and vacuum dried at 50° C. for about 4 hours to obtain 1.5 kg of a supported catalyst.
[0324] Preparation Examples 2 to 4
[0325] Each hybrid metallocene catalyst was prepared in the same manner as Preparation Example 1, except that the types and mixing molar ratios of the first transition metal compound and the second transition metal compound were changed as shown in Table 1 below.
[0326] Comparative Preparation Example 1
[0327] A hybrid metallocene catalyst comprising bis(n-butylcyclopentadienyl)-zirconium dichloride (C-2) and tert-butoxyhexylmethylsilyl(N-tert-butylamino)(2,3,4,5-tetramethylcyclopentadienyl)titanium dichloride (C-3) was prepared in the same manner as Preparation Example 1 of Korean Patent Publication No. KR10-2016-0010351.
[0328] The loading amount of the first transition metal compound in the prepared hybrid metallocene compound is 0.1 mmol / g·support, and the loading amount of the second transition metal compound is 0.1 mmol / g·support.
[0329]
[0330] Comparative Preparation Example 2
[0331] A hybrid metallocene catalyst was prepared in the same manner as in Preparation Example 1, except that the types and mixing molar ratios of the first transition metal compound and the second transition metal compound were changed as shown in Table 1 below.
[0332] [Table 1]
[0333]
[0334] Preparation of polyethylene
[0335] Examples 1 to 4 and Comparative Examples 1 to 2
[0336] As a polymerization reactor, a 140L continuous polymerization reactor with a reaction flow rate of about 7 m / s was prepared, in which an isobutylene slurry loop process was capable of being performed. Then, the reactants required for polyethylene polymerization described in Table 2 were continuously introduced into the reactor. As the catalyst used in each polymerization reaction, the catalyst prepared in the preparation example or comparative preparation example described in Table 1 was used, and the catalyst was mixed with the isobutylene slurry and then introduced. The polymerization reaction was carried out at a pressure of about 40 bar and a temperature of about 85°C.
[0337] Other main conditions of the polymerization reaction are shown in Table 2.
[0338] [Table 2]
[0339]
[0340] In Table 2, the activity (kgPE / kgSiO2·hr) was calculated as the ratio of the weight of supported catalyst used (kg) to the weight of polymer produced (kgPE) per unit time (hr).
[0341] In addition, the input amount of 1-hexene (wt%) was calculated as the percentage of the input amount of 1-hexene based on the total weight of monomers including ethylene and 1-hexene, and the input amount of hydrogen (ppm) was based on the total weight of monomers including ethylene and 1-hexene.
[0342] Experimental Example 1
[0343] Physical properties of polyethylenes prepared in Examples and Comparative Examples were measured as follows and the results are shown in Table 3. For comparison, commercial polyethylene Exceed XP 8656 (manufactured by Exxonmobile Chemical) was used as Comparative Example 3 and BO1801 (manufactured by DAELIM) was used as Comparative Example 4.
[0344] (1) Melt index (MI) 2.16 ): measured according to ASTM D1238 (Condition E, 190°C, 2.16 kg load) standard.
[0345] (2) Density: measured according to ASTM D1505.
[0346] (3) SCBD characteristics
[0347] The polyethylenes prepared in the Examples and Comparative Examples were subjected to cross fractionation chromatography (CFC) analysis by the following method.
[0348] [Cross fractionation chromatography (CFC) measurement conditions (including TREF and GPC analysis)]
[0349] -Analysis equipment: Polymer Char CFC-7890B (G3440D)
[0350] (Detector: Integrated detector IR5 MCT)
[0351] -Sample preparation and injection: 32 mg of the polyethylene prepared in the examples or comparative examples was placed in a 10 mL vial, then placed in an autosampler, 8 mL of 1,2,4-trichlorobenzene (TCB) was added, dissolved at 160° C. for 90 minutes, and then stabilized at 140° C. for 20 minutes. After nitrogen purging, the sample was extracted and loaded into a temperature rising elution fractionation column (TREF column).
[0352] - Crystallization: The temperature of the sample previously loaded into the TREF column was set to 140°C, then cooled from 140°C to 35°C at a rate of 0.5°C / min and held for 15 minutes.
[0353] The specific conditions for stability and crystallization are as follows:
[0354]
[0355] - Temperature Rising Elution Fractionation (TREF) analysis: A previously crystallized sample is heated at a rate of 1°C / min from 35°C to 120°C until it is below the fraction temperature, then fixed, and the concentration of the fraction eluted at this temperature for 5 minutes is measured. A TREF curve is derived from the concentration measurement results.
[0356] The content ratios (wt%) of the soluble fraction (SF) eluted in the region where the elution temperature is lower than 35°C (<35°C), the polymer fraction (M1) eluted in the region where the elution temperature is higher than 35°C and lower than 70°C (35°C to 70°C), and the polymer fraction (M3) eluted in the region where the elution temperature is higher than 90°C (>90°C) are calculated from the TREF curve respectively.
[0357] <Fraction Temperature>
[0358] 35°C / 40°C / 43°C / 46°C / 49°C / 52°C / 55°C / 58°C / 61°C / 64°C / 67°C / 70°C / 73°C / 76°C / 79°C / 82°C / 85°C / 88°C / 91°C / 94°C / 97°C / 100°C / 105°C / 120°C
[0359] <Measurement Conditions>
[0360]
[0361] - GPC analysis: The fractions eluted at each temperature in the previous TREF analysis were transferred to the GPC column of a GPC device (PL - GPC220), and then GPC analysis was performed under the following analysis conditions to measure the molecular weight of the eluted molecules. In addition, the number of SCBs (short - chain branches, chain branches containing 2 to 7 carbon atoms per 1000 carbon atoms) of the molecules eluted at each temperature was measured using a PerkinElmer Spectrum100FT - IR connected to the GPC device.
[0362] <Sample Preparation>
[0363] Polyethylene was pretreated by dissolving it in 1,2,4 - trichlorobenzene at 160°C for 10 hours to prepare a concentration of 10 mg / 10 mL, and then supplied in an amount of 200 μL.
[0364] <GPC Analysis Conditions>
[0365] GPC device: Waters PL - GPC220
[0366] GPC column: Polymer Laboratories PLgel MIX - B column with a length of 300 mm
[0367] Measurement temperature: 160°C
[0368] Solvent: 1,2,4 - trichlorobenzene
[0369] Flow rate: 1 mL / min
[0370] Standard sample: Polystyrene standard sample
[0371] (Weight-average molecular weights of polystyrene standard specimens: 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 200000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol, and 10000000 g / mol, a total of 9 kinds)
[0372] <FT-IR analysis conditions>
[0373] Measuring device: PerkinElmer Spectrum 100
[0374] Measuring temperature: 160 °C
[0375] Wavenumber: 2700 cm -1 to 3000 cm -1
[0376] Number of scans: 16
[0377] Resolution: 8 cm -1
[0378] Detector: DTGS
[0379] <Measuring conditions>
[0380]
[0381]
[0382] Specifically, the weight-average molecular weight (Mw) of the low-crystalline polymer fraction (M1) eluted in the region where the elution temperature is above 35 °C and below 70 °C was measured by GPC analysis respectively (M1 Mw , g / mol), the Mw of the medium-crystalline polymer fraction (M2) eluted in the region where the elution temperature is higher than 75 °C and lower than 90 °C (M2 Mw , g / mol), and the Mw of the high-crystalline polymer fraction (M3) eluted in the region where the elution temperature is higher than 90 °C or higher (M3 Mw , g / mol). In addition, based on the measurement results, the ratio of the weight-average molecular weight of the high-crystalline polymer fraction to the polymer fraction eluted in the region where the elution temperature is above 90 °C (M3) to the weight-average molecular weight of the low-crystalline polymer fraction (M1) eluted in the region where the elution temperature is below 70 °C (M3 Mw / M1 Mw ) was calculated. The results are shown in Table 3 below and Figure 1 .
[0383] Figure 1A graph showing the relationship between the elution temperature (Te) (°C) and the weight average molecular weight (Mw) (g / mol) of each eluted polymer obtained from the CFC analysis results of the polyethylene of Examples 1 to 4 and Comparative Examples 1 to 4 is shown, from which the molecular weight distribution according to the crystal distribution can be determined.
[0384] In addition, the measurement results were plotted with the elution temperature (Te) as the horizontal axis and the SCB number as the y-axis, and the plot was fitted using data analysis software (Origin Pro, 9.1) to obtain a first-order linear relationship. The absolute value of the slope of the obtained first-order linear relationship was taken as the SCB slope. The results are shown in Table 3 and Figure 2a and 2b middle.
[0385] Figure 2a is a graph showing the relationship between the elution temperature (Te) (°C) and the SCB amount (CH3 / 1000C) based on the CFC analysis results of the polyethylene of Examples 1 to 4, Figure 2b This is a graph showing the relationship between the elution temperature (Te) (°C) and the SCB amount (CH3 / 1000C) based on the CFC analysis results of the polyethylenes of Comparative Examples 1 to 4.
[0386] from Figure 2a and Figure 2b It can be determined that the SCB distribution varies with the crystal distribution, and it can be confirmed that Te has a linear relationship with SCB.
[0387] [Table 3]
[0388]
[0389] [Table 4]
[0390]
[0391] Experimental Example 2
[0392] The rheological properties of the polyethylene prepared in the examples and comparative examples were measured, and the relaxation time spectra were analyzed using the results. The relaxation spectrum index (RSI) was then obtained according to the method proposed by Wasserman (SH Wasserman ANTEC 1997, 55, 1129).
[0393] In addition, the ER (polydispersity at high MW) and PDR (overall polydispersity) of the polyethylenes of Examples and Comparative Examples were obtained using the measurement results of rheological properties.
[0394] (1) Sample preparation
[0395] Each of the polyethylenes prepared in Examples and Comparative Examples was compression-molded at 182° C. for 3 minutes to prepare each sample for measuring rheological properties.
[0396] Specifically, the polyethylene in Examples and Comparative Examples was melted at 182° C. under a pressure of 2 bar for 1 minute, then quenched in a cooling press under a pressure of 100 bar for 2 minutes to prepare a disc-shaped compression molded sample of 2 mm in thickness×25.4 mm in diameter.
[0397] Meanwhile, when preparing the sample, 1500 ppm antioxidant (Songnox 1076 (Songwon): Songnox 1680 (Songwon) weight ratio = 1:2) and 300 ppm processing aid (3MDynamar polymer processing additive FX5929) were added and mixed based on the total weight of the polyethylene, and then extruded and pelletized at an extrusion temperature of 190° C. at an extrusion rate of 35 kg / hr using a twin screw extruder (TEK 30MHS, manufactured by SMPLATECH, with a diameter of 32 pi, L / D = 40) to facilitate loading the sample into the rheometer and minimize degradation or crosslinking during sample re-measurement, because the polyethylene of Examples 1 to 4 and Comparative Examples 1 and 2 was in a powdered state. However, no antioxidant was added to the sample (e.g., the polyethylene in Comparative Example 3) that already contained an antioxidant and a processing aid in a commercially available pelletizing process.
[0398] (2) Rheological property measurement
[0399] The storage modulus (G') and loss modulus (G") of the polyethylenes of Examples and Comparative Examples were measured using a rotational rheometer (ARES-G2 rheometer, manufactured by TA Instruments) in a frequency sweep mode.
[0400] Specifically, in order to minimize the decomposition of polyethylene, the test chamber of the rheometer was purged with nitrogen and the rheometer was preheated to an initial temperature of 190°C. After sample loading and oven equilibration, the prepared sample was placed between the parallel plates of the rheometer (plate diameter: 25.4mm, gap between plates: 2mm) and compressed to a thickness of 2.0mm. Under a nitrogen atmosphere, vacuum shear flow was applied at a strain rate of 5% in each frequency range from 0.05rad / s to 500rad / s. At this time, the strain was set to within 5% to meet the linear viscoelastic condition. A total of 8 minutes passed from inserting the sample between the plates to starting the frequency scan (0.03rad / s to 100rad / s), and the measurement was performed at 190°C. At the same time, a new sample was used at each temperature, and nitrogen (N2) was circulated in the test chamber for each measurement.
[0401] Through the above-mentioned measurement, the storage modulus (G') and the loss modulus (G") with respect to the frequency (ω) were obtained.
[0402] (3) Relaxation time spectrum analysis
[0403] Based on the measured results of rheological properties in (2), the relationships between dynamic modulus (G'(ω) and G"(ω)) and frequency (ω) were determined respectively.
[0404]
[0405] In equations (3) and (4), N represents the mode number of the relaxation spectrum modal distribution, ω represents the frequency (rad / s), and τ i represents the discrete relaxation time (s), G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ).
[0406] Further, the modal distribution of the relaxation spectrum was calculated using IRIS rheology software (manufactured by IRIS Development), and then the first moment of the distribution (G I ) and the second moment (G II ).
[0407]
[0408] In equations (i) and (ii), N represents the number of modes in the modal distribution of the relaxation time spectrum, τi represents the relaxation time (s), and G represents the modulus corresponding to the relaxation time (dyne / cm 2 ).
[0409] Using the G calculated above I and G II The relaxation spectrum index (RSI) was obtained according to the following equation 1.
[0410] [Equation 1]
[0411]
[0412] Furthermore, using the values determined above and the results of the relaxation time spectrum analysis, the weighted average relaxation time (τ w ) and zero shear viscosity (η0) (Pa·s).
[0413] [Equation 2]
[0414]
[0415] [Equation 3]
[0416]
[0417] In Equation 2 and Equation 3, N represents the number of modes in the relaxation time spectrum modal distribution, τi represents the relaxation time (s), and G iRepresents the modulus corresponding to the relaxation time (dyne / cm 2 ).
[0418] In addition, based on the above measurement results, the relaxation time (τ) is used as the horizontal axis and τH(τ) / η0 is used as the y-axis to obtain the relaxation time spectrum. The continuous data of the relaxation time spectrum is divided by η0 for normalization, and then deconvolution is performed to obtain the crystal distribution, relaxation time spectrum Max and FWHM (full width at half maximum). In addition, the area ratio (peak area between 1s≤τ≤10s / total peak area) is also obtained. Among them, the peak area between 1s≤τ≤10s and the total peak area are obtained by integration, respectively.
[0419] Figure 3 The relaxation time spectra of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 measured using a rotational rheometer are shown; in addition, Figures 4 to 11 They are shown respectively Figure 3 Deconvolution graphs of relaxation time spectra of Examples 1 to 4 and Comparative Examples 1 to 4. In this regard, deconvolution was performed according to the Gaussian + Lorentzian method using the peak analyzer of the Origin program (Origin 2022 version) (P. Yu, Spectroscopy 20 (2006), 229-251).
[0420] (4) ER and PDR measurements
[0421] The rheological properties of (2) were measured according to the method described in "New measures of polydispersity from rheological data on polymermelts", Journal of Appied Polymer Science, Vol. 57, 1605-1626 (1995), and the ER (high MW polydispersity) and PDR (bulk polydispersity) of the polyethylene of the examples and comparative examples were obtained, respectively.
[0422] Specifically, using the storage modulus (G') and loss modulus (G") obtained from the measurement results of (2), log(G") and log(G') were plotted on the x-axis and y-axis, respectively, and the plotted graphs were curve-fitted using data analysis software (OriginPro). As a result, the following linear relationship (5) was obtained.
[0423] logG'=k1+k2logG” (5)
[0424] In the equation, k1 and k2 are constants for curve fitting, respectively.
[0425] Next, ER is obtained by interpolating the G' value corresponding to G"ref as shown in the following Equation 7.
[0426] [Equation 7]
[0427] ER = C1G′ | at G″ref
[0428] In equation 7,
[0429] C1 represents the constant 1.781x10 -3 ,
[0430] G' represents the storage modulus of polyethylene (dyne / cm 2 ),as well as
[0431] G"ref represents the loss modulus of polyethylene, which is 5000 dyne / cm 2 , which is a small modulus value corresponding to the low-frequency region.
[0432] When the minimum G" value is greater than 5000 dyne / cm 2 When , ER was obtained by extrapolation.
[0433] Furthermore, PDR (overall polydispersity) was calculated according to the following Equation 8.
[0434] [Equation 8]
[0435]
[0436] In Equation 8, η*1, η*2, and η*3 represent the reference complex modulus G * ref1 , G * ref2 and G * ref3 Complex viscosity of linear polymer G * ref1 =1.95x10 4 dyn / cm 2 , G * ref2 =(G * ref1 G * ref3 ) 1 / 2 , and log10(G * ref3 / G * ref1 )=2, and obtain η * 1. η * 2 and η * 3.
[0437] In addition, the complex viscosity (η*) was calculated according to the following equation 10 using the measurement results of ARES.
[0438] [Equation 10]
[0439]
[0440] In Equation 10, ω represents frequency (rad / s), G' represents storage modulus (dyne / cm 2 ), G' represents the loss modulus (dyne / cm 2 ).
[0441] at the same time, Fig.12 A graph showing the relationship between the loss modulus (G") and the storage modulus (G') measured by ER obtained from the measurement results of the rheological properties of the polyethylene of Examples 1 to 4 and Comparative Examples 1 to 4 is shown, and Fig.13 A graph showing the relationship between the storage modulus (G') and the complex viscosity (η*) measured by PDR obtained from the measurement results of the rheological properties of the polyethylenes of Examples 1 to 4 and Comparative Examples 1 to 4 is shown.
[0442] [Table 5]
[0443] Example 1 Example 2 Example 3 Example 4 Crystal distribution type Twin Peaks Twin Peaks Twin Peaks Twin Peaks RSI 42.01 31.15 36.81 29.19 <![CDATA[τ w (s)]]> 9.781 1.226 5.883 1.287 <![CDATA[η0(Pa·s)]]> 12650 9990 11500 9200 Relaxation time of the largest peak in the relaxation time spectrum (s) 0.131 0.098 0.131 0.174 FWHM of peak with 1s≤τ≤10s 0.99 1.22 1.90 1.29 Peak area ratio of 1s≤τ≤10s (%) 14.2 26.0 35.0 23.4 ER 0.86 0.76 0.86 0.76 PDR 6.9 5.7 6.4 6.0
[0444] [Table 6]
[0445] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Crystal distribution type Single Peak Twin Peaks Single Peak Single Peak RSI 16.16 15.43 48.54 22.67 <![CDATA[τ w (s)]]> 0.568 0.378 1.161 0.659 <![CDATA[η0(Pa·s)]]> 7200 7300 16700 7700 Relaxation time of the largest peak in the relaxation time spectrum (s) 0.305 0.032 0.032 0.099 FWHM of peak with 1s≤τ≤10s 2.64 2.52 ND ND Peak area ratio of 1s≤τ≤10s (%) 34.8 23.4 ND ND ER 0.22 0.13 0.47 0.32 PDR 2.5 2.2 7.4 4.6
[0446] In the table, “ND” means not detected.
[0447] Experimental Example 3
[0448] The crystal distribution characteristics of the polyethylene prepared in the examples and comparative examples were evaluated by sequential self-nucleation and annealing (SSA) analysis. The results are shown in Table 5 below.
[0449] Each polyethylene was heated from 30° C. to 180° C. using a differential scanning calorimeter (equipment name: DSC8000, manufacturer: PerkinElmer) and then maintained at 180° C. for 20 minutes to eliminate all thermal history of the sample before measurement.
[0450] Next, cool down from 180°C to 140°C, keep at 140°C for 20 minutes, cool down from 140°C to 30°C, keep at 30°C for 1 minute, and heat again. Polyethylene is heated to 135°C, which is 5°C lower than the initial heating temperature of 140°C, and then kept at 135°C for 20 minutes, and then cool down from 135°C to 30°C, keep at 30°C for 1 minute, and heat again. In this way, the n+1th annealing temperature is 5°C lower than the nth annealing temperature, the holding time and cooling temperature are the same, and heating-annealing-cooling is repeated, while gradually reducing the heating temperature until it reaches 50°C. At this time, the heating rate and cooling rate are controlled at 20°C / min respectively. Finally, the temperature is raised from 0°C to 180°C at a rate of 10°C / min, the heat change is observed, and the SSA temperature spectrum is measured.
[0451] The Tm and heat (area S) of each melting peak in the measured SSA thermogram were used. i ) quantified peak area. That is, for the total peak area (f1+f2+f3) of the melting peak in the SSA thermogram, the content ratios of f2 / f1, f3 / f1, and f3 / f2 of each area are calculated using the areas of the three regions f1 (melting temperature below 100°C), f2 (melting temperature above 100°C and below 120°C), and f3 (melting temperature above 120°C).
[0452] At the same time, the area of each peak was calculated by integration.
[0453] Further, the heterogeneity (I) of the ethylene sequence was calculated according to the following equation 6:
[0454] [Equation 6]
[0455] Inhomogeneity (I) = L w / L n
[0456] In Equation 6, L w represents the weighted average of ethylene sequence length (ESL) (unit: nm), L n It represents the arithmetic mean value of ESL (unit: nm).
[0457] The weighted average value (L) of the ethylene sequence in Equation 6 was calculated according to the following Equations 4 and 5: w ) and the arithmetic mean (L n ):
[0458] [Equation 4]
[0459]
[0460] [Equation 5]
[0461]
[0462] In equations 4 and 5,
[0463] S i represents the area of each melting peak measured in the SSA heat map, and
[0464] L i represents the average ethylene sequence length (ASL) corresponding to each melting peak in the SSA heat map.
[0465] In addition, the ASL can be calculated based on the measured SSA thermogram with reference to Journal of Polymer Science Part B: Polymer Physics 2002, Vol. 40, 813-821 and Journal of the Korean Chemical Society 2011, Vol. 55, No. 4.
[0466] [Table 7]
[0467]
[0468] Experimental Example 4
[0469] In order to evaluate the processing characteristics of the polyethylenes prepared in Examples and Comparative Examples, the head pressure, output volume, and output index were measured, respectively.
[0470] (1) Head pressure
[0471] When a polyethylene film is produced using a blow molding extruder, a pressure intensifier is installed in front of the die and filter assembly of the blow molding extruder to measure the head pressure (bar) of the polyethylene.
[0472] Specifically, based on the total weight of the polyethylene prepared in the embodiment or the comparative example, 1500ppm of an antioxidant (weight ratio of Songnox 1076 (Songwon): Songnox 1680 (Songwon) = 1:2) and 300ppm of 3MDynamar Polymer Processing Additive FX5929 were added, and after mixing, a twin-screw extruder (TEK 30MHS, manufactured by SMPLATECH, diameter 32pi, L / D=40) was used to extrude at an extrusion temperature of 190°C and an extrusion rate of 35kg / hr to prepare 18kg of a composition for producing a granular film.
[0473] A single screw extruder (Eugene Engineering, Blown Film M / C, 50pi, L / D=32) was used as a blow molding extruder to extrude the above-prepared composition for producing a film at an extrusion temperature of 130° C. to 180° C., while adjusting the extrusion speed from 8 m / min to 10 m / min to achieve a final thickness of 50 μm. At this time, the die gap was 2.0 mm, the die diameter was 120 mm, and the blow ratio was 2.5.
[0474] The extruder of the laboratory scale blown film line has a die diameter of 120 mm, a die gap of 1.5 mm (0.060 inches), a barrel screw diameter of 50 pi, and a mixer at the end of the screw. The screw speed of the extruded composition is 40 rpm, the frost line height (FLH) is 200 mm to 250 mm, the barrel and die set temperature is 170 ° C, and the melt temperature is 185 ° C to 190 ° C. Cooling is carried out at 20 ° C using a dual lip air-ring. The reason for choosing these specific processing conditions is that the film properties obtained thereby represent the film properties obtained under larger scale commercial film blowing conditions.
[0475] When the blown film was produced under the above conditions, the head pressure (bar) was measured using a booster installed in front of the die and a filter group of the blown film extruder.
[0476] (2) Output
[0477] In addition, the film production process was carried out in the same manner as above, but the screw speed of the blow molding extruder was fixed at 40 rpm, and the take-out speed was adjusted to make the film thickness 50 μm. When a stable state was reached, the output (g / min) extruded from the blow molding extruder within 1 minute was measured.
[0478] (3) Output index
[0479] Using the measurement results of the head pressure and the output amount in (1) and (2), the output index g / (min·bar) was calculated according to the following equation 9.
[0480] [Equation 9]
[0481] Output index = blow molding extruder 1 minute output (g / min) / head pressure (bar)
[0482] [Table 8]
[0483]
[0484] Experimental Example 5
[0485] Films were prepared using the polyethylenes prepared in Examples and Comparative Examples, respectively, and the dart impact strength and haze were measured.
[0486] (1) Film production
[0487] Based on the total weight of the polyethylene prepared in the embodiment or comparative example, 1500 ppm of an antioxidant (weight ratio of Songnox 1076 (Songwon): Songnox 1680 (Songwon) = 1:2) and 300 ppm of 3M Dynamar Polymer Processing Additive FX5929 were added, and after mixing, a twin-screw extruder (TEK 30MHS, manufactured by SMPLATECH, diameter 32pi, L / D=40) was used to extrude at an extrusion temperature of 190°C and an extrusion rate of 35 kg / hr to prepare 18 kg of a composition for producing a granular film.
[0488] The composition for film production prepared above was subjected to inflation molding under the following film extrusion conditions to produce a film.
[0489] <Film Forming Conditions>
[0490] Single screw extruder (YOOJIN ENGINEERING, Blown Film M / C, 50pi, L / D=32)
[0491] Melting temperature (or extrusion temperature): 185℃
[0492] Die gap: 2.0mm
[0493] Mould diameter: 120mm
[0494] Blowing rate: 2.5
[0495] Frost line height: maintained at 200mm to 250mm
[0496] Sample output: 300g / min to 500g / min
[0497] Cooling: Use double air ring
[0498] Film thickness: 50μm
[0499] (2) Dart impact strength
[0500] For each polyethylene film of the examples and comparative examples prepared above, the dart impact strength was measured according to ASTM D1709 [Method A], and each film sample was repeated 5 times (20 times / 1 group), and then the average value was calculated.
[0501] (3) Haze
[0502] For the films having a thickness of 50 μm prepared as described above, the haze of each film was measured according to ISO 13468 standard.
[0503] [Table 9]
[0504]
[0505] The test results show that the films of Examples 1 to 4 exhibit higher impact strength and significantly lower haze than the films of Comparative Examples 1 to 4.
Claims
1. A polyethylene, wherein When the polyethylene is subjected to temperature-increasing elution fractionation and Fourier transform infrared spectroscopy analysis, the absolute value of the slope a in the first-order linear relationship y=ax+b obtained from the curve of the change of the SCB (short chain branch) amount with the elution temperature is 0.5 to 0.6, and Density measured according to ASTM D1505 is 0.916 g / cm 3 Up to 0.920g / cm 3 .
2. The polyethylene according to claim 1, when subjected to temperature-raising elution fractionation, satisfies the following conditions (a1) to (a3): (a1) weight average molecular weight (Mw) of the polymer fraction (M1) eluted at an elution temperature of 35° C. to 70° C.: 110,000 g / mol or more; (a2) weight average molecular weight (Mw) of the polymer fraction (M3) eluted at an elution temperature of 90° C. or higher: 110,000 g / mol or higher; and (a3) The Mw ratio of the weight average molecular weight of M3 to the weight average molecular weight of M1 (M3 Mw / M1 Mw ): 0.9 or above.
3. The polyethylene according to claim 1, wherein When the polyethylene is subjected to relaxation time spectrum analysis, the polyethylene exhibits a bimodal crystal distribution in a graph with relaxation time (τ) as the x-axis and τH(τ) / η0 as the y-axis.
4. The polyethylene according to claim 1, wherein When the polyethylene is subjected to relaxation time spectrum analysis, the relaxation spectrum index (RSI) of the polyethylene is 29 to 43, which is calculated according to the following equation 1: [Equation 1] In equation 1, G is calculated according to the following equations (i) and (ii) respectively: I and G II , In equations (i) and (ii), N represents the number of modes in the modal distribution of the relaxation time spectrum, G i Represents the modulus corresponding to the relaxation time (dyne / cm 2 ), τ i represents the relaxation time (s).
5. The polyethylene according to claim 1, wherein When the polyethylene is subjected to relaxation time spectrum analysis, the weighted average relaxation time (τ w ) is 1.2 seconds to 10 seconds, and The highest peak of the relaxation time spectrum appears when the relaxation time (τ) is between 0.05 s and 1 s.
6. The polyethylene according to claim 1, wherein When the polyethylene is subjected to relaxation time spectrum analysis, the FWHM (full width at half maximum) of the peak at a relaxation time (τ) of 1 to 10 seconds is 0.95 to 2.0, and The ratio of the area of the peak to the total peak area of the relaxation time spectrum (peak area of relaxation time of 1 second to 10 seconds / total peak area of relaxation time spectrum) is 14% to 40%.
7. The polyethylene according to claim 1, wherein When the polyethylene is subjected to SSA (Continuous Self Nucleation and Annealing) analysis, the polyethylene satisfies the following conditions (c1) to (c3): (c1) f1 (<100°C) (ratio of the peak area with melting temperature below 100°C to the total peak area): 0.35 to 0.41; (c2) f2 (100-120°C) (ratio of the peak area with a melting temperature of 100°C to 120°C to the total peak area): 0.30 to 0.38; (c3)f3 (>120°C) (ratio of the peak area with melting temperature higher than 120°C to the total peak area): 0.24 to 0.
33.
8. The polyethylene according to claim 7, wherein When the polyethylene is subjected to SSA analysis, the polyethylene further satisfies the following conditions (c4) to (c6): (c4) f2 / f1: 0.7 to 0.9; (c5) f3 / f1: 0.6 or more; (c6)f3 / f2: 0.8 or more.
9. The polyethylene according to claim 1, wherein When the polyethylene is subjected to SSA analysis, the heterogeneity (I) of the ethylene sequence calculated according to the following Equation 6 is 1.4 to 1.5: [Equation 6] Inhomogeneity (I) = Lw / Ln In equation 6, Lw represents the weighted average value of ESL (ethylene sequence length) (unit: nm), L n It represents the arithmetic mean value of ESL (unit: nm).
10. The polyethylene according to claim 9, wherein Lw is 15 nm to 30 nm, and Ln is 12 nm to 20 nm.
11. The polyethylene according to claim 1, wherein The polyethylene has an ER (polydispersity at high MW) of greater than 0.7, which is determined according to the following Equation 7: [Equation 7] In equation 7, C1 represents the constant 1.781×10 -3 , G' represents the storage modulus of polyethylene (dyne / cm 2 ),as well as G” ref Indicates the loss modulus of polyethylene 5000dyne / cm 2 .
12. The polyethylene according to claim 1, wherein The polyethylene has a PDR (bulk polydispersity) greater than 5.0, which is determined according to the following Equation 8: [Equation 8] In Equation 8, η*1, η*2, and η*3 represent the reference complex modulus G * ref1 , G * ref2 and G * ref3 The complex viscosity, which is based on G* ref1 =1.95×10 4 dyn / cm 2 , G * ref2 =(G * ref1 G * ref3 ) 1 / 2 and log10(G * ref3 / G * ref1 )=2calculation.
13. The polyethylene according to claim 1, wherein The head pressure of the polyethylene is 210 bar to 260 bar.
14. The polyethylene according to claim 1, wherein The polyethylene output index is above 1.60 g / (min·bar), which is calculated according to the following equation 9, [Equation 9] Output index = blow molding extruder 1 minute output (g / min) / head pressure (bar).
15. The polyethylene according to claim 1, wherein The melt index (MI) of polyethylene was measured according to ASTM D1238 at a temperature of 190°C and a load of 2.16 kg. 2.16 ) is 0.5g / 10min to 1.5g / 10min.
16. The polyethylene according to claim 1, wherein The polyethylene is an ethylene / 1-hexene copolymer.
17. A film comprising the polyethylene of claim 1.
18. The film according to claim 17, wherein The film has a dart impact strength of 1900 gf or more measured according to ASTM D 1709 Method A at a BUR (Blow Up Ratio) of 2.3 to 3 and a film thickness of 45 to 55 μm, and a haze of 14% or less measured according to ISO 13468 standard.
Citation Information
Patent Citations
Ethylene-1-hexene-1-butene terpolymer and film comprising the same
KR1020160010351A
Method for preparing supported hybrid metallocene catalyst, and supported hybrid metallocene catalyst using the same
KR1020160067508A
Polyolefin
KR1020220067494A